Absorbent article with conforming features

By using the absorbent core structure of the upper and lower nonwoven layers and the inner core layer in the absorbent product, combined with cellulose fibers and superabsorbent particles, the problem of insufficient liquid absorption and conformability is solved, and the absorption of the absorbent product is realized. Comprehensive improvement of conformity and comfort.

CN119451654APending Publication Date: 2025-02-14PROCTER & GAMBLE CO
View PDF 57 Cites 0 Cited by

Patent Information

Application Number
CN202380041287.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-18
Filing Date
2023-05-17
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing absorbent products have shortcomings in liquid absorption and conformability, especially while maintaining absorption characteristics and comfort, it is difficult to take into account both wet elasticity and conformability.

Method used

An absorbent core structure is adopted, including an upper and lower nonwoven layer and an inner core layer, which contains cellulose fibers and superabsorbent particles, and the overall performance of the absorbent core structure is enhanced through the structural bonding site.

Benefits of technology

It achieves a comprehensive improvement in liquid absorption, conformability and comfort of absorbent products, maintains good absorption characteristics, and provides wet elasticity and conformability, improving the user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451654A_ABST
    Figure CN119451654A_ABST
Patent Text Reader

Abstract

A disposable absorbent article has a topsheet, a backsheet, and an absorbent core structure disposed therebetween. The absorbent core structure includes an upper non-woven layer comprising polymeric fibers and having a basis weight of about 35 gsm to about 85 gsm; a lower nonwoven layer comprising polymeric fibers and having a basis weight of from about 10 gsm to about 40 gsm; and an inner core layer disposed between the upper nonwoven layer and the lower nonwoven layer. The inner core layer comprises from about 50% to about 85% cellulose fibers by weight of the inner core layer, and from about 15% to about 50% superabsorbent particles by weight of the inner core layer. The absorbent core structure has an average density of between about 0.045 g / cm3 and about 0.15 g / cm3. The inner core layer is contained within the nonwoven layer by substantially sealing at least a left side region and a right side region of the upper nonwoven layer and the lower nonwoven layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention is directed to absorbent articles having conforming features and improved elastic structures. Background Art

[0002] Absorbent articles such as diapers, training pants, feminine pads, adult incontinence pads, etc. are widely used by consumers. Generally speaking, absorbent articles such as these include a top sheet and a back sheet, wherein an absorbent core structure is disposed between the top sheet and the back sheet. Historically, absorbent core structures for catamenial pad applications have utilized cellulosic fibers in various ways to control the complex and varying rheological properties of menstrual fluids and vaginal discharges.

[0003] First method comprises the thick absorbent core based on cellulose (also referred to as " fluff " or " pulp "), and it can be hard, bulky, and suffers from structural collapse due to the short fiber length of cellulose (<2.5mm), particularly when loaded with fluid, because cellulose fiber softens when wetted.Over time, these thick absorbent cores rich in cellulose have been made thinner, including absorbent polymer materials, such as absorbent gelling materials (" AGM "), to further improve their absorption characteristics.However, these absorbent core structures have lower mechanical strength, and even more can not keep their shape, particularly when loaded with liquid effluent.These absorbent core structures can form crackle and tear and gather (permanent deformation shape) when in use.These thinner structures tend to be even denser (therefore harder), and are often wrapped in simple cellulose tissue or thin nonwoven layer to keep AGM inside, and reduce core tearing and undesirable gathering when in use.

[0004] Other approaches combine these wrapped cellulose and AGM cores with additional fluid acquisition-distribution layers (above the fluid storage core) to further improve the performance of these simple wrapped cores. The additional acquisition-distribution layer also serves to improve the integrity of the wrapped core and some degree of tearing and gathering. However, these acquisition-distribution layers are not ideal for complex viscous fluids that need to move across the boundaries between these layers. In order to better facilitate the distribution of fluid from the acquisition-distribution system to the fluid storage wrapped cellulose and AGM cores, the core can be densified to increase capillary action and the ability to effectively draw fluid from the acquisition-distribution layer above. However, the cost of densifying such an absorbent system is comfort (stiffness) and the ability of the absorbent core structure and / or absorbent article to easily conform to the unique anatomical geometry of the wearer.

[0005] Another material for absorbent core structure includes airlaid core. Airlaid cores are typically composed of cellulose, AGM and synthetic binder fibers to enhance wet integrity, and are typically composed of a surface coating of a polymer (such as latex) to reduce dust during product manufacturing. Because these materials are manufactured offline at a separate supplier and need to be transported and introduced into a fast-moving production line, they are highly dense and hard. Densification and synthetic binder fibers provide higher wet integrity during use, and due to higher capillary action, can help promote fluid transport from the acquisition-distribution layer to the airlaid core. However, due to the high bending stiffness, this may again be at the expense of comfort (rigidity) and the ability to easily conform to the wearer's unique anatomical geometry.

[0006] Therefore, it would be beneficial to have an improved absorbent article including an absorbent core structure that addresses the tradeoffs of comfort conformability and wet resilience while maintaining good absorbent properties. Also, it would be beneficial to provide methods for forming such articles without sacrificing the performance properties of the product. Summary of the invention

[0007] Disclosed herein is a disposable absorbent article comprising: a top sheet; a back sheet; and an absorbent core structure disposed between the top sheet and the back sheet, wherein the absorbent core structure comprises: an upper nonwoven layer comprising polymer fibers and having a basis weight of about 35 gsm to about 85 gsm; a lower nonwoven layer comprising polymer fibers and having a basis weight of about 10 gsm to about 40 gsm; and an inner core layer disposed between the upper nonwoven layer and the lower nonwoven layer. woven layers, wherein the inner core layer comprises about 50% to about 85% cellulose fibers by weight of the inner core layer, and about 15% to about 50% superabsorbent particles by weight of the inner core layer; wherein the absorbent core structure has an average density between about 0.045 g / cm3 and about 0.15 g / cm3; wherein the inner core layer is contained within the upper nonwoven layer and the lower nonwoven layer by substantially sealing at least the left and right regions of the upper nonwoven layer and the lower nonwoven layer at a peripheral seal.

[0008] The present invention also discloses a disposable absorbent article, which includes: a top sheet; a back sheet; and an absorbent core structure, which is arranged between the top sheet and the back sheet, wherein the absorbent core structure has a front area, a middle area and a back area and includes: an upper nonwoven layer, the upper nonwoven layer contains polymer fibers and has a basis weight of about 35 gsm to about 85 gsm; a lower nonwoven layer, the lower nonwoven layer contains polymer fibers and has a basis weight of about 10 gsm to about 40 gsm; and an inner core layer, which is arranged between the upper nonwoven layer and the lower nonwoven layer; wherein the inner core layer contains a mixture of cellulose fibers and superabsorbent particles, wherein the absorbent core structure includes a plurality of structural bonding sites; wherein the structural bonding sites have a thickness of about 2 mm 2 To about 5mm 2 and wherein the total structural bond area of ​​the absorbent core structure is from about 0.75% to about 4.5% of the absorbent core structure, as measured according to the Structural Bond Site Pattern Spacing and Area Measurement Method. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 is a schematic diagram of an absorbent core structure according to the present disclosure.

[0010] Figure 2A is a schematic diagram of an absorbent article according to the present disclosure.

[0011] Figure 2B is another schematic illustration of an absorbent article according to the present disclosure.

[0012] Figure 2C is another schematic illustration of an absorbent article according to the present disclosure.

[0013] Figure 3 It is a cross section of the absorbent core structure.

[0014] Figure 4 is a close-up illustration of a structural bonding site in accordance with the present disclosure.

[0015] Figure 5 yes Figure 4 Cross section of a structural bonding site.

[0016] Figure 6 is a cross-section of an absorbent article according to the present disclosure.

[0017] 7A to 7C It is a test method arrangement for wet and dry CD ultra-sensitive 3-point bending method.

[0018] Figure 8 , Fig.9A and Fig. 9B It is a test method arrangement for wet and dry bunching compression testing.

[0019] Fig. 10A and Fig. 10B is an exemplary graph of gather curves produced by wet and dry gather compression tests. Fig. 10A and Fig. 10B The graphs in are shown to illustrate how the calculations in the method may be performed and do not represent the data described herein. DETAILED DESCRIPTION

[0020] As used herein, "disposable absorbent article" or "absorbent article" shall be used with reference to articles such as diapers, training pants, diaper pants, refastenable pants, adult incontinence pads, adult incontinence pants, feminine hygiene pads, cleansing pads, and the like, each of which is intended to be discarded after use.

[0021] As used herein, "absorbent core structure" shall be used with reference to an upper nonwoven layer, a lower nonwoven layer, and an inner core layer disposed between the upper nonwoven layer and the lower nonwoven layer.

[0022] As used herein, "hydrophilic" and "hydrophobic" have the meanings generally accepted in the art with respect to the contact angle of water on the surface of a material. Thus, a material having a water contact angle greater than about 90 degrees is considered hydrophobic, and a material having a water contact angle less than about 90 degrees is considered hydrophilic. A hydrophobic composition will increase the contact angle of water on the surface of a material, while a hydrophilic composition will decrease the contact angle of water on the surface of a material. Although described above, reference to relative hydrophobicity or hydrophilicity between a material and a composition, between two materials, and / or between two compositions does not mean that a material or composition is hydrophobic or hydrophilic. For example, a composition may be more hydrophobic than a material. In this case, neither the composition nor the material may be hydrophobic; however, the contact angle exhibited by the composition is greater than the contact angle of the material. As another example, a composition may be more hydrophilic than a material. In this case, neither the composition nor the material may be hydrophilic; however, the contact angle exhibited by the composition may be less than the contact angle exhibited by the material.

[0023] As used herein, the term "filament" refers to any type of continuous strand produced by a spinning process, a meltblowing process, a melt fibrillation or film fibrillation process, or an electrostatic spinning process, or any other suitable process for preparing a filament. The term "continuous" in the context of filaments is distinguished from short-length fibers in that the short-length fibers are cut into specific target lengths. In contrast, "continuous filaments" are not cut into predetermined lengths, but instead, they can be broken into random lengths, but are typically much longer than short-length fibers.

[0024] As used herein, "machine direction" refers to the direction in which the fiber web flows through the absorbent article conversion process. For simplicity, the machine direction may be referred to as "MD".

[0025] As used herein, "cross direction" refers to the direction perpendicular to the MD. For simplicity, the cross direction may be referred to as "CD".

[0026] As used herein, "elastic" refers to a material that tends to retain its shape in both dry and wet states and when subjected to a compressive force tends to recover its original pre-compressed shape when such force is removed. In some aspects, the upper and / or lower nonwoven layers described herein may be elastic.

[0027] As used herein, "wearer-facing" (sometimes referred to herein as body-facing) and "outward-facing" (sometimes referred to herein as garment-facing) refer to the relative position of an element or the relative position of a surface of an element or a group of elements, respectively. "Wearer-facing" means that an element or surface is closer to the wearer than some other element or surface during wear. "Outward-facing" means that an element or surface is farther from the wearer than some other element or surface during wear (i.e., the element or surface is near the wearer's clothing, which may be worn over the absorbent article).

[0028] It should be understood that each maximum numerical limitation given throughout this specification includes each lower numerical limitation, as if such lower numerical limitations were expressly written herein. Each minimum numerical limitation given throughout this specification will include each higher numerical limitation, as if such higher numerical limitations were expressly written herein. Each numerical range given throughout this specification will include each narrower numerical range falling within such wider numerical range, as if such narrower numerical ranges were all expressly written herein.

[0029] Disposable absorbent article as herein described comprises top sheet, back sheet and absorbent core structure, and this absorbent core structure comprises upper nonwoven layer and lower nonwoven layer, and wherein inner core layer is arranged between upper nonwoven layer and lower nonwoven layer.Inner core layer can be contained in nonwoven layer by sealing at least left area and right area of ​​upper nonwoven layer and lower nonwoven layer at perimeter seal place substantially.In some configurations, upper nonwoven layer and lower nonwoven layer can be engaged at perimeter seal place that extends around the whole periphery of inner core layer.

[0030] In some configurations, disposable absorbent articles may include the following structure (from the surface facing the wearer to the surface facing outward): top sheet, upper nonwoven layer, inner core layer, lower nonwoven layer and back sheet. In some respects, the top sheet may be in direct contact with the upper nonwoven layer, the upper nonwoven layer may be in direct contact with the inner core layer, and / or the inner core layer may be in direct contact with the lower nonwoven layer. So-called "direct contact" means that there is no other intermediate component layer between the corresponding layers in direct contact with it. However, it is not excluded that adhesive materials may be arranged between at least a portion of the above-mentioned layers.

[0031] like Figure 1 and Figure 3As shown, the absorbent core structure 10 may include an upper nonwoven layer 210 and a lower nonwoven layer 220 (also collectively referred to herein as an upper nonwoven layer and a lower nonwoven layer or an upper nonwoven and a lower nonwoven) and an inner core layer 200 disposed between the upper nonwoven layer 210 and the lower nonwoven layer 220. The absorbent core structure 10 may include an inner core layer 200, which includes a liquid-absorbing material. Without being limited by theory, it is believed that the absorbent core structure can recover its dry or wet shape in a certain range of body movements and compression. The liquid-absorbing material may include a matrix comprising cellulose fibers and superabsorbent particles, sometimes referred to herein as "fluff / AGM". The upper nonwoven layer 210 and the lower nonwoven layer 220 may be joined together at the perimeter seal 230 with glue or other conventional bonding methods, including but not limited to ultrasonic bonding, fusion bonding, curling, and combinations thereof.

[0032] The flexibility and / or elasticity of the absorbent core structure causes the absorbent article to conform comfortably to the wearer's anatomical geometry while effectively managing the fluid as it leaves the body. This can be unexpectedly achieved without typical densification hardening (for wet integrity) by utilizing an elastic upper nonwoven layer and lower nonwoven layer composed of an elastic polymer located above and below the loosely packed fluff / AGM matrix of the inner core layer. When the absorbent core structure becomes wet, this absorbent core structure is able to carry structural loads and recover shape without physically hardening or losing desired structural properties.

[0033] It is believed that when the elastic upper nonwoven and lower nonwoven of selection are positioned above and below the fluff / AGM matrix of the inner core layer and are joined to the fluff / AGM matrix on and around, wet integrity / shape stability is produced in the absorbent core structure rich in cellulose, and there is no significant densification and hardening result. Upper nonwoven and lower nonwoven need enough restoring forces to bring the fluff / AGM matrix back to the original state or stable fiber orientation state after compression. Wrapping or encapsulating the fluff core rich in cellulose with simple cellulose tissue or the less elastic nonwoven material may not show enough recovery energy to recover shape in use and particularly when wetting. The structure wet elastic nonwoven described in detail herein can show the recovery energy enough to recover the fiber matrix rich in cellulose after compression, and is selected to deliver high compression recovery with relatively low stiffness under dry and wet state.

[0034] The nonwoven layer of top can have the basis weight of about 30gsm to about 85gsm or about 35gsm to about 70gsm or about 40gsm to about 60gsm.The nonwoven layer of top can have the tensile rigidity of about 0.3N / mm to about 1.6N / mm.The nonwoven layer of top can have the breaking strain greater than about 10% or about 10% to about 50% or about 20% to about 40%.The nonwoven layer of top can have the permanent strain of about 0.005mm / mm to about 0.013mm / mm or 0.005mm / mm to about 0.0090mm / mm.

[0035] The nonwoven layer of the bottom part can have the basis weight of about 10gsm to about 40gsm, or about 15gsm to about 20gsm. The nonwoven layer of the bottom part can have the tensile rigidity of about 0.2N / mm to about 1.6N / mm. The nonwoven layer of the bottom part can have the strain at break greater than about 10%, or about 10% to about 50%, or about 20% to about 40%. The nonwoven layer of the bottom part can have the permanent strain of about 0.005mm / mm to about 0.013mm / mm.

[0036] The upper nonwoven layer and the lower nonwoven layer may include polymer fibers. Suitable upper nonwoven fibers and lower nonwoven fibers may be selected from PET (polyethylene terephthalate), PP (polypropylene), BiCo (bicomponent fibers) selected from PE / PP (PE sheath and PP core) and / or PE / PET (PE sheath PET core), PLA (polylactic acid), and combinations thereof.

[0037] Suitable upper nonwovens may comprise from about 60% to about 100%, or from about 70% to about 100% synthetic fibers, or from about 0% to about 40%, or from about 0% to about 30% regenerated cellulose fibers, such as rayon and / or viscose.

[0038] The upper nonwoven layer can comprise staple fiber length greater than about 10mm or greater than about 25mm or about 10mm to about 100mm or about 20mm to about 75mm or about 25mm to about 50mm. The upper nonwoven layer can comprise fiber diameter is about 1.3 dtex to about 10 dtex, alternatively about 1.3 dtex to about 6.0 dtex, alternatively about 2.0 dtex to about 5.0 dtex. In some configurations, the upper nonwoven layer can comprise fiber, wherein the fiber is a blend of staple fibers having a fiber diameter of about 2.0 dtex to about 10 dtex.

[0039] The lower nonwoven layer can comprise a fiber having a length greater than about 10mm or greater than about 25mm or about 10mm to about 100mm or about 20mm to about 75mm or about 25mm to about 50mm. In some configurations, the lower nonwoven layer can comprise continuous fibers. The lower nonwoven layer can comprise a fiber diameter that is about 1.3 dtex to about 5.0 dtex, alternatively about 1.3 dtex to about 3.3 dtex, alternatively about 1.3 dtex to about 2.2 dtex, alternatively about 2.0 dtex to about 10 dtex. In some configurations, the lower nonwoven layer can comprise a fiber, wherein the fiber is a blend of fibers having a fiber diameter that is about 0.1 dtex to about 6.0 dtex.

[0040] In some configurations, a suitable fiber combination may include an upper nonwoven polymer fiber having a diameter of about 2.0 dtex to about 10 dtex and a lower nonwoven polymer fiber having a diameter of about 1.7 dtex to about 5 dtex. In some configurations, a suitable fiber combination may include an upper nonwoven polymer fiber having a diameter of about 1.3 dtex to about 2.2 dtex and a lower nonwoven polymer fiber having a diameter of about 1.7 dtex to about 5 dtex.

[0041] See also Figure 2A and Figure 3 , the absorbent article 20 may include an absorbent core structure 10 including an upper nonwoven layer 210 and a lower nonwoven layer 220 with an inner core layer 200 disposed therebetween. Figure 2A 2 is a top view of an absorbent article 20 with the topsheet removed for simplicity. Figure 3 is a cross-sectional view of an absorbent core structure 10.

[0042] Absorbent article 20 and absorbent core structure 10 include front region 21, back region 23 and middle region 22 arranged in the middle of front region and back region respectively.Upper nonwoven layer 210 may include left region 210a and right region 210b, and lower nonwoven layer 220 may include left region 220a and right region 220b.Upper nonwoven layer 210 and lower nonwoven layer 220 may extend outwards from inner core layer periphery 200a and may be joined together to form perimeter seal 230.In some configurations, whole inner core layer 200 may be located at the inner side of perimeter seal 230.Perimeter seal 230 may help to seal the absorbent material of inner core layer 200 in upper nonwoven layer 210 and lower nonwoven layer 220.Perimeter seal 230 may include at least first transverse sealing area 231 and second transverse sealing area 231 '. In some configurations, the perimeter seal 230 may also include a front perimeter seal area 232 and / or a rear perimeter seal area 233. In some configurations, the perimeter seal 230 may extend around the entire inner core layer perimeter 200a. In some configurations, the perimeter seal 230 may extend partially around the inner core layer perimeter 200a.

[0043] In some configurations, the inner core layer 200 can be contained within the upper nonwoven layer 210 and the lower nonwoven layer 220 by substantially sealing at least the left side regions 210a, 220a and the right side regions 210b, 220b of the upper nonwoven layer 210 and the lower nonwoven layer 220. In some configurations, the inner core layer 200 can be contained within the upper nonwoven layer 210 and the lower nonwoven layer 220 by sealing at least a portion of the left side regions 210a, 220a and the right side regions 210b, 220b of the upper nonwoven layer 210 and the lower nonwoven layer 220.

[0044] The perimeter seal 230 may have a seal width WS between about 1 mm and about 10 mm, or between about 2 mm and about 8 mm, or between about 3 mm and about 6 mm. The seal width WS may be uniform or may vary around the perimeter of the inner core layer.

[0045] In some configurations, absorbent article 20 may also include a front end seal 234 positioned in the front end region 227 of absorbent article and a rear end seal 235 positioned in the rear end region 228 of absorbent article. Front end seal 234 and / or rear end seal 235 may seal top sheet, upper nonwoven layer, lower nonwoven layer and back sheet together. In some configurations, front end seal 234 and / or rear end seal 235 may seal top sheet and back sheet. In some configurations, front end seal 234 and / or rear end seal 235 may be curled seals.

[0046] In some configurations, the upper nonwoven layer 210 and the lower nonwoven layer 220 can be discrete materials, which can be cut into the size and shape of the inner core layer 200, so that it can be fitted between the top sheet and the back sheet, but can not extend to the front seal 234 or the rear seal 235 basically. In some configurations, the inner core layer 200, the upper nonwoven layer 210 and / or the lower nonwoven layer 220 can be shaped, which means that it is non-rectangular. In some configurations, the upper nonwoven layer 210 and / or the lower nonwoven layer 220 can extend from the front end area 227 of the absorbent article, pass the front end seal 234 and the rear end seal 235, and arrive at the rear end area 228 of the absorbent article.

[0047] When being attached to the fluff / AGM substrate by applying a core construction adhesive, the nonwoven layer comprising polymer fibers can maintain its shape and resist plasticization when wetted, and the core construction adhesive is applied directly to the fluff / AGM substrate or applied to the elastic nonwoven layer via conventional spraying, and the conventional spraying application is selected to achieve bonding but not interrupting the flow of fluid to the fluff / AGM substrate. In addition, the upper nonwoven layer 210 and the lower nonwoven layer 220 may have at least a portion of the peripheral seal 230 to better connect the upper nonwoven layer 210 and the lower nonwoven layer 220 with the inner core layer 200 contained in the upper nonwoven layer 210 and the lower nonwoven layer 220. The peripheral seal 230 may be positioned in at least the middle region 22 of the absorbent article 20 and / or the absorbent core structure 10. Not limited by theory, it is believed that the middle region 22 (between the thighs of the wearer during use) can withstand the most frequent and / or maximum force during use. It has been found that the presence of at least a portion of the perimeter seal at the left and right regions of the upper and lower nonwoven layers outside the fluff / AGM matrix, where the upper and lower nonwoven layers are bonded by conventional means (e.g., adhesives, polymer welding and / or strong physical entanglement), can help ensure that the upper and lower nonwovens retain their structural function and do not separate during physical deformation, thereby limiting any potential integrity and bunching issues. Producing the perimeter seal can allow any excess nonwoven material to be removed so that the absorbent core structure can be shaped to conform to the inner thigh geometry.

[0048] The nonwoven layer material of suitable upper part and lower part can bend and recover its original shape along with bending force.Thin or highly flexible material is easy to bend under low peak force (load) and low bending energy.Although unsuitable material is easy to bend, it does not have enough recovery energy, and therefore keeps the bending state of deformation due to insufficient recovery energy.Suitable material has enough energy to recover its initial pre-bent state.Material with enough bending recovery energy can be considered as elastic upper nonwoven layer and lower nonwoven layer.

[0049] As described above, the upper nonwoven and the lower nonwoven may include polymer fibers. The polymer fibers may be included to help provide the structural integrity of the upper nonwoven and the lower nonwoven. The polymer fibers may help improve the structural integrity of the upper nonwoven and the lower nonwoven in the machine direction (MD) and the cross direction (CD), which may facilitate web handling during the handling of the upper nonwoven and the lower nonwoven to be incorporated into the pad.

[0050] The polymer fiber of any appropriate component can be selected.Some examples of suitable polymer fibers can include bicomponent fibers or polyethylene terephthalate and copolyethylene terephthalate components comprising polyethylene (PE) and polyethylene terephthalate (PET) components. The components of bicomponent fibers can be configured to sheath-core configuration, side-by-side configuration, eccentric sheath-core configuration, trilobal arrangement or any other desired configuration. In some configurations, polymer fibers can include bicomponent fibers with PE / PET components, which are configured to have concentric sheath-core configurations, wherein the polyethylene component forms a sheath.

[0051] The PE sheath component of the core fiber structure of the sheath core fiber is used to provide the elasticity of the upper nonwoven and the lower nonwoven. In the synergistic combination, the PE sheath component with a lower melting temperature than the PET core component can be used to provide inter-fiber melting / fusion bonding, which is achieved via the thermal treatment of the precursor batt. This can help to provide tensile strength to the web in MD and CD. This inter-fiber bonding can be used to reduce the sliding between the fiber and the fiber, thereby further helping to give the material shape stability and elasticity, even when the material is wetted.

[0052] In the case of relatively high weight fractions of polymer fibers, more connections can be created within the structure via heat treatment. However, too many connection points may impart greater stiffness to the upper and lower nonwovens than desired. For this reason, selecting the weight fraction of polymer fibers may involve prioritizing and balancing the competing demands for stiffness and softness in the upper and lower nonwovens.

[0053] As mentioned above, the upper nonwoven and the lower nonwoven can additionally include polymer fibers, which increase the elasticity of the upper nonwoven and the lower nonwoven. Elastic polymer fibers can help the upper nonwoven and the lower nonwoven to keep permeability and compression recovery. In some configurations, the upper nonwoven and the lower nonwoven can include elastic polymer fibers with variable cross-sections (for example, circular and hollow spirals), and / or can include elastic fibers with different sizes.

[0054] The polymer fiber can be elastic and can be spun from any suitable thermoplastic resin, such as polypropylene (PP), polyethylene terephthalate (PET), or other suitable thermoplastic fibers known in the art. The average staple length of the elastic polymer fiber can be selected to be greater than about 10 mm, about 20 mm to about 100 mm, or about 30 mm to about 50 mm, or about 35 mm to about 50 mm. The elastic polymer fiber can have any suitable structure or shape. For example, the elastic polymer fiber can be circular or have other shapes, such as spiral, fan-shaped elliptical, trilobal, fan-shaped belt, etc. In addition, the elastic polymer fiber can be solid, hollow, or hollow at multiple locations. The elastic polymer fiber can be solid and circular in shape. In other suitable examples, the elastic polymer fiber includes polyester / coextruded polyester fiber. Other suitable examples of elastic polymer fibers can include bicomponent fibers, such as polyethylene / polypropylene, polyethylene / polyethylene terephthalate, polypropylene / polyethylene terephthalate bicomponent fibers. These bicomponent fibers can have a sheath / core configuration.

[0055] The elastic polymer fiber can also be polyethylene terephthalate (PET) fiber or other suitable non-cellulose fibers known in the art. PET fibers can be given any suitable structure or shape. For example, the PET fiber can be round or have other shapes, such as spiral, fan-shaped elliptical, trilobal, fan-shaped belt, hollow spiral, etc. PET fibers can be solid, hollow or multiple hollows. In a specific example, the cross section of the PET fiber can be hollow and have a curved or spiral structure along their length. Optionally, the elastic polymer fiber can be spirally curled or flatly curled. The elastic polymer fiber can have an average curl count of about 4 to about 12 curls / inch (cpi), or about 4cpi to about 8cpi, or about 5cpi to about 7cpi, or about 9cpi to about 10cpi. Specific non-limiting examples of elastic polymer fibers can be obtained from Wellman, Inc (Ireland) with trade names H1311 and T5974. Other examples of suitable elastic polymer fibers are disclosed in US7,767,598.

[0056] The reinforcing polymer fibers and the elastic polymer fibers should be carefully selected. For example, although the constituent polymers forming the reinforcing polymer fibers and the elastic polymer fibers may have similarities, the elastic polymer fiber composition should be selected so that the melting temperature of their components is higher than the melting temperature of the bondable components of the reinforcing polymer fibers. Otherwise, during the heat treatment, the elastic polymer fibers may bond to the reinforcing polymer fibers, and vice versa, thereby forming an overly rigid structure. To avoid this risk, where the reinforcing polymer fibers include bicomponent fibers, for example, core-sheath construction fibers having a sheath component with a relatively low melting temperature, at which melting temperature fusion bonding will occur, the elastic polymer fibers may include only the constituent chemical components of the core, which may be a polymer with a relatively high melting temperature.

[0057] Nonwoven performance can be affected by the combination of nonwoven fiber polymer selection, fiber characteristics and fiber arrangement or connection mode. Nonwoven selection can affect the ability of absorbent articles to recover their shape after compression, bending and extension (stretching) forces that exist with body movement in use. If the fibers are short fibers (less than about 10mm), they may be irreversibly rearranged under extension and compression forces. The rearrangement of fibers in the fiber matrix (changing their orientation / state) dissipates the tensile (elongation) or compression force, so that the energy used to affect the deformation is no longer available for recovery to the original shape. Longer fiber networks (usually greater than about 10mm but less than about 100mm) can dissipate the typical tensile / compression forces along the fiber length and through the structure in body movement. Therefore, the applied force can be used to restore the structure to its original state. Longer fiber networks composed of finer fibers (less than about 15 to about 20 microns and about 2.0 dtex) are more likely to stretch and compress. Thus, the fluff / AGM structure can be deformed more easily (and to a greater degree), but the energy associated with these deformations is relatively small and insufficient to bring the structure back to its original state. Thicker fibers (such as greater than about 2.0 dtex to about 10 dtex) are flexible under body forces but provide sufficient fiber and web recovery energy to return the structure to its original state.

[0058] From a structural point of view, the fiber arrangement in the long fiber network can affect the performance of absorbent articles containing these nonwovens. Long fiber webs of thicker fibers are generally more bulky than conventional thin spunbond nonwoven webs composed of closely spaced and physically bonded continuous fine fibers. Webs that produce thicker fibers arranged in a more random orientation (such as those that can be achieved via carding, hydroentanglement, and needle punching) can stretch and compress, whereby the fibers only temporarily adjust their arrangement (there are spaces between the fibers for these arrangements) and can carry / store deformation forces, and this energy can be used to restore the structural shape.

[0059] Additionally, the finer (less than about 2.0 dtex) synthetic fibers (such as BiCo and PP fibers) typically found in spunbond are closely spaced, relatively parallel aligned, and tightly bonded together. The bonded fibers within these spunbond webs are so interconnected (with closely spaced point bonds) that during stretching (elongation), the fibers at the polymer level are forced to stretch, which causes the polymer chains within the fibers to permanently rearrange, and thus the fibers themselves potentially remain permanently elongated (permanently strained) and can no longer recover to their original state.

[0060] In some configurations, the polymer fibers in the upper nonwoven layer and the polymer fibers of the lower nonwoven layer can be different. In some configurations, the polymer fibers of the upper nonwoven layer and the polymer fibers of the lower nonwoven layer can be the same.

[0061] Examples of suitable nonwoven materials include, but are not limited to, the following: (i) 40 gsm carded elastic nonwoven material produced by Yanjan, China (material code; ATB Z87G-40-90), which is a carded nonwoven composed of a blend of 60% 2 dtex and 40% 4 dtex BiCo (PE / PET) fibers. The fibers are bonded (ATB = through "hot" air bonding) to produce a wet elastic network. The material basis weight is 40 gsm and its thickness (at 7 kPa) is about 0.9 mm. Without being limited by theory, it is believed that due to the presence of 4 dtex BiCo fibers and a fiber-to-fiber bonded BiCo network, the material has low permanent strain (less than about 0.013 mm / mm) and sufficient dry recovery energy (greater than about 0.03 N*mm) in wet and dry CD ultrasensitive 3-point bend methods; (ii) 55 gsm elastic spunlace material produced by Sandler Germany (Material Code: 53FC041001), which is a hydroentangled nonwoven, which is produced via a carding step (such as the nonwoven described above) followed by hydroentanglement with an elevated drying step (such as described in U.S. Patent Publication No. 2020 / 0315873A1), which produces an entangled and BiCo bonded elastic network. It contains a fiber blend of 30% 10 dtex HS-PET, 50% 2.2 dtex BiCo (PE / PET) and 20% 1.3 dtex rayon. Thus, in both wet and dry CD ultrasensitive 3-point bending methods, the material has low permanent strain (less than about 0.013 mm / mm) and sufficient dry recovery energy (greater than about 0.03 N*mm); and (iii) a 50 gsm elastic spunlace material produced by Sandler Germany (Material Code: 53FC041005opt82), which is a hydroentangled nonwoven produced via a carding step (as described above for the nonwoven), followed by hydroentanglement with an elevated drying step (as described in U.S. Patent Publication No. 2020 / 0315873A1), which produces an entangled and BiCo-bonded elastic network. It comprises a fiber blend of 60% 5.8 dtex BiCo (PE / PET), 20% 3.3 dtex trilobal "structural" rayon and 20% 1.3 dtex rayon. Therefore, the material has low permanent strain (less than about 0.013 mm / mm) and sufficient dry recovery energy (greater than about 0.03 N*mm) in wet and dry CD ultrasensitive 3-point bending methods. Although the material has 40% rayon that can soften when wet, the use of structural trilobal rayon fibers helps structural stability in the wet state.

[0062] In conjunction with adjusting pore size, volume, and number by selecting appropriate fiber size, basis weight, and degree of consolidation, manufacturers may wish to select fiber components with specific surface chemistries, for example, fibers with hydrophobic surfaces, hydrophilic surfaces, or blends of different fibers and / or z-direction stratifications or gradients thereof. Fibers with hydrophilic surfaces will tend to attract and move the aqueous components of menstrual fluid along them in a manner that is conducive to wicking and rapid fluid acquisition after discharge. However, at the same time, the predominance of hydrophilic fiber surfaces within the topsheet may increase the tendency of the topsheet to reacquire fluid (rewet) from the absorbent assembly below, which may result in an undesirable sensation of wetness for the user. On the other hand, fibers with hydrophobic surfaces will tend to repel the aqueous components of menstrual fluid and / or resist the movement of fluid along their surfaces, thereby tending to resist wicking, but also resisting rewetting. For any particular product design, the manufacturer may wish to seek the appropriate balance in selecting constituent fibers having hydrophilic surfaces, fibers having hydrophobic surfaces, or blends and / or z-direction layering thereof, combined with fiber size, fiber consolidation level, and the resulting topsheet pore size, volume, and number.

[0063] The inner core layer is produced in the air-laid process. The flow of cellulose fiber and AGM is carried on the fast-moving airflow, and is deposited in the pocket of the three-dimensional shape on the rotary forming drum, and the rotary forming drum has a vacuum below to suck cellulose and AGM into the pocket in the shelving station. The pocket of this shape provides the actual physical shape of the absorbent core structure. The upper nonwoven or the lower nonwoven can be first introduced on the forming drum, and the upper nonwoven or the lower nonwoven is pulled into a three-dimensional pocket shape under vacuum. In this case, the cellulose and AGM material flow is directly deposited on the top (or the lower nonwoven) in the forming station. Before entering the forming station, the nonwoven is coated with an adhesive to provide a stronger connection between cellulose and AGM and nonwoven layers. When leaving the shelving section, the second remaining nonwoven layer is combined with the nonwoven carrying cellulose and AGM layer leaving the shelving section. This second remaining nonwoven (upper nonwoven or lower nonwoven, depending on which nonwoven is advanced through the resting section) is pre-coated with adhesive to achieve perimeter seals and better integrate cellulose and AGM without hindering liquid from flowing into the cellulose and AGM matrix. In another method, the nonwoven is not first introduced into the forming station, and the cellulose and AGM agglomerate is maintained on the forming drum under vacuum until it is sprayed onto the upper nonwoven layer or lower nonwoven layer with the adhesive applied as described in detail above, and then sealed with the second remaining nonwoven to produce an absorbent core structure. The width of the upper nonwoven web and the lower nonwoven web is generally selected to be wider than the maximum width of the formed cellulose and AGM matrix, so as to achieve an effective perimeter seal at the junction of the two nonwovens at least on the leftmost and rightmost sides of the absorbent core structure.

[0064] The inner core layer may comprise any of a variety of liquid-absorbent materials commonly used in absorbent articles, such as comminuted wood pulp (commonly referred to as airfelt). One suitable absorbent core material is an airfelt material available from Weyerhaeuser Company (Washington, USA) under the code FR516. Examples of other suitable liquid-absorbent materials that may be used in the absorbent core may include creped cellulose wadding; meltblown polymers including coforms; chemically stiffened, modified or crosslinked cellulose fibers; synthetic fibers such as crimped polyester fibers; peat moss; cotton, bamboo; absorbent polymer materials; or any equivalent material or combination of materials, or mixtures thereof.

[0065] Absorbent polymer materials used in absorbent articles generally comprise water-insoluble, water-swellable, hydrogel-forming, cross-linked absorbent polymers which are capable of absorbing large quantities of liquids and of retaining such absorbed liquids under moderate pressures.

[0066] The absorbent polymer material used in the absorbent core according to the present disclosure may include superabsorbent particles, also referred to as "superabsorbent materials" or "absorbent gelling materials". The absorbent polymer material (usually in particle form) may be selected from polyacrylates and polyacrylate-based materials, such as, for example, partially neutralized, cross-linked polyacrylates. The term "particle" refers to granules, fibers, flakes, spheres, powders, sheets, and other shapes and forms known to those skilled in the art of superabsorbent particles. In some aspects, the superabsorbent particles may be in the shape of fibers, i.e., elongated needle-shaped superabsorbent particles.

[0067] In some configurations, the inner core layer may include cellulose fibers and superabsorbent particles. The inner core layer may include all cellulose fibers of about 50% to 85% by weight of the inner core layer, or about 55% to about 80% or about 60% to about 75%. The inner core layer may include all superabsorbent particles of about 10% to about 50% by weight of the inner core layer, or about 15% to about 50% or about 20% to about 40% or about 25% to about 35%. Preferably, the inner core layer may include cellulose fibers of about 125gsm to about 400gsm.

[0068] In some configurations, the inner core layer may contain from about 50% to about 85% cellulose fibers and from about 15% to about 50% superabsorbent particles. The resulting absorbent core structure may have a viscosity between about 0.045 g / cm 3 and about 0.15g / cm 3 Between, and / or between 0.045g / cm 3 and 0.12g / cm 3 The absorbent article may have an average density between about 0.045 g / cm 3 and about 0.16g / cm3 The average density between .

[0069] After the compression step, the absorbent core structure can be compressed and recover their original shape. Suitable absorbent core structures require lower compression forces (less resistance), and when the user compresses and releases the compression forces in a cyclic manner with various body movements, the structure can recover its shape. To achieve this, the structure maintains enough recovery energy after multiple cycles of compression. In the absence of enough recovery energy, the structure remains in a compressed gathered state without enough force (stored energy) to recover.

[0070] like Figure 1 , FIG. 2A to FIG. 2C , Figure 4 and Figure 5 As shown, the absorbent core structure may include a plurality of structural bonding sites 15. The structural bonding sites 15 may be symmetrical and / or asymmetrical and may be any shape, including but not limited to circular, oval, heart-shaped, diamond-shaped, triangular, square, star-shaped and / or X-shaped. The structural bonding sites 15 may be on the absorbent article and / or on the absorbent core structure. In some configurations, the structural bonding sites may have a width of about 2 mm. 2 To about 5mm 2 In some configurations, the total structural bonding area can be about 0.5% to about 5% of the absorbent core structure, or about 0.75% to about 4.5%, or about 1% to about 4%, as measured according to the structural bonding site pattern spacing and area measurement method. In some configurations, the total structural bonding area can be about 1% to about 4% of the absorbent article, as measured according to the structural bonding site pattern spacing and area measurement method. The average distance between the structural bonding sites can be about 10mm to about 32mm. In some configurations, the average distance between the structural bonding sites can be greater than about 20mm. In some configurations, the structural bonding sites can have a maximum width of about 1mm to about 6mm, or about 1.5mm to about 5mm, or about 2mm to about 4mm. Not limited by theory, it is believed that the average distance between the structural bonding sites and / or the size of the structural bonding sites can help maintain the structural integrity of the absorbent core structure without producing undesirable rigidity that can inhibit the ability of the absorbent article to conform to the body.

[0071] In some configurations, the structural bonding sites can be distributed across absorbent articles and / or absorbent core structures, or they can be gathered in the region of absorbent articles and / or absorbent core structures. In some configurations, the structural bonding sites can be gathered in the middle region 22 of absorbent articles and / or absorbent core structures. In some configurations, the middle region 22 of absorbent articles and / or absorbent core structures can not have structural bonding sites and can be surrounded by the area of ​​structural bonding sites and / or embossing. In some configurations, absorbent articles can include one or more flexure bonding channel regions 160, wherein the flexure bonding channel region can be the embossing of continuous depression and / or a series of closely spaced individual compressions.

[0072] In some configurations, the structural bonding sites 15 can join the top sheet 110, the upper nonwoven layer 210, the absorbent core structure 10, and the lower nonwoven layer 220. In some configurations, the structural bonding sites 15 can join the upper nonwoven layer 210, the absorbent core structure 10, and the lower nonwoven layer 220.

[0073] Suitable absorbent articles and / or absorbent core structures may include an upper nonwoven layer and a lower nonwoven layer that are closer together in the Z direction at the structural bonding sites, but are not melted together. Since these structural bonding sites are not melted together, they may not be permanent in nature, but may be entangled with the material in the structural bonding sites. In some configurations, the structural bonding sites may be substantially free of fusion bonding.

[0074] While the shape of the structural bonding site may be any shape, suitable shapes may be more elaborate shapes, such as asymmetric shapes (as opposed to simple points).

[0075] The absorbent article 20 can be elastic and conformable and can deliver an excellent use experience without substantial bunching and / or compression. The absorbent article can be exposed to body forces and can return to its original state. The absorbent article can have a resistance between about 0.07 N / mm 2 and 0.30N / mm 2 Between, or about 0.10N / mm 2 To about 0.25N / mm 2 , or about 0.10N / mm 2 To about 0.20N / mm 2 CD dry modulus as measured in wet and dry CD and MD 3-point bend method.

[0076] The absorbent article may have a dry thickness of between about 2.0 mm and about 6.0 mm, or about 2.0 mm to about 4.5 mm, or about 2.5 mm to about 4.0 mm, or about 2.75 mm to about 3.5 mm, as measured according to the wet and dry CD and MD 3-point method. In some configurations, the absorbent article may have a dry thickness of between about 0.07 N / mm 2 and 0.30N / mm 2 and a dry thickness between about 2.0 mm and about 4.5 mm, as measured according to the wet and dry CD and MD 3-point method, or between about 0.10 N / mm 2 To about 0.25N / mm 2 CD dry modulus between about 2.50 mm and about 4.0 mm dry thickness, or between about 0.10 N / mm 2 To about 0.20N / mm 2 The absorbent article may have a CD dry modulus between about 10.0 N*mm and a dry thickness of about 2.75 mm to about 3.5 mm. 2 To about 30.0N*mm 2 , or about 10.0N*mm 2 and about 25.0N*mm 2 , or about 10N*mm 2 To about 20N*mm 2 , or about 13N*mm 2 To about 20N*mm 2 CD dry bending stiffness between about 10.0 N*mm and about 10.0 N*mm, as measured in wet and dry CD and MD 3-point bend method. Particularly suitable absorbent articles include those having a CD dry bending stiffness between about 10.0 N*mm and about 10.0 N*mm. 2 and about 30.0N*mm 2 and a dry thickness of about 2.5 mm to about 4.0 mm (as measured according to the wet and dry CD and MD 3-point method), or a CD dry bending stiffness of about 10 N*mm 2 To about 25N*mm 2 and a dry thickness between about 2.5 mm and 4.0 mm, or a CD dry bending stiffness of about 13 N*mm 2 To about 30N*mm 2 And those absorbent articles having a dry thickness of from about 2.75 mm to about 3.5 mm.

[0077] The absorbent article may have a fifth cycle wet recovery energy of about 1.0 N*mm to 3.5 N*mm, or about 1.5 N*mm to about 3.0 N*mm, or about 1.5 N*mm to about 2.8 N*mm. Particularly suitable absorbent articles may have a fifth cycle wet recovery energy between about 1.0 N*mm and 3.5 N*mm and a fifth cycle wet recovery % of about 29% to about 40%, or a fifth cycle wet recovery energy of about 1.5 N*mm to about 3.0 N*mm and a fifth cycle wet recovery % of about 29% to about 40%, or a fifth cycle wet recovery energy of about 1.5 N*mm to about 2.75 N*mm and a fifth cycle wet recovery % of about 29% to about 40%.

[0078] Absorbent articles including absorbent core structures as disclosed herein may also need to deliver a dry touch to consumers after adding fluid, as measured by the touch rewet method. Absorbent core structures and absorbent articles that meet the above characteristics are designed to conform more closely and more completely to the complex anatomical genital shapes of the wearer comfortably and gently. Therefore, such absorbent articles may also need to be dry to the touch after excretion so as not to irritate sensitive genital tissues. Therefore, the absorbent articles described herein may also maintain a touch rewet value of less than about 0.15 grams, or less than about 0.12 grams, or about 0 to about 0.15 grams, or about 0 to about 0.12 grams.

[0079] like FIG. 2A to FIG. 2C As shown, the absorbent article 20 also includes a base structure 100, which includes an absorbent core structure 10. As shown, the absorbent core structure 10 and / or the inner core layer 200 may include a generally hourglass shape. However, any suitable shape may be utilized. Some examples include an offset hourglass shape (one end is wider than the opposite end, and the middle portion between the two ends is narrowed), a bicycle seat shape (one end and the center portion are narrower than the second end), etc. The side edges 120 and 125 may follow the general outline of the absorbent core structure. Therefore, in the case where the absorbent core structure has an hourglass shape, the side edges of the absorbent articles 120 and 125 may also be arranged in an hourglass shape. However, it is envisioned that the side edges 120 and 125 are generally straight or slightly curved so that they do not follow the outline of the absorbent core structure. Additional details will be discussed below. The absorbent article 20 may be symmetrical about the longitudinal centerline 80 or asymmetrical about the longitudinal centerline 80. Similarly, the absorbent article 20 may be symmetrical about the transverse centerline 90 or asymmetrical about the transverse centerline 90.

[0080] Top sheet

[0081] The top sheet 110 may be formed from any suitable nonwoven web or formed film material (see Figure 6). Referring back to the drawings, the topsheet 110 is positioned adjacent to the wearer-facing surface of the absorbent article 20 and may be joined thereto and to the backsheet 130 by any suitable attachment or bonding method. The topsheet 110 and the backsheet 130 may be directly joined to each other in the peripheral region outside the periphery of the absorbent core structure, and may be indirectly joined by joining them directly to the wearer-facing surface and the outward-facing surface of the absorbent article, respectively, or to additional optional layers included in the absorbent article.

[0082] The absorbent article 20 can have any known otherwise effective top sheet 110, such as a compliant, soft-feeling, and non-irritating top sheet to the wearer's skin. Suitable top sheet materials will include liquid-permeable materials that are comfortable when in contact with the wearer's skin and allow discharged menstrual fluid to penetrate quickly through. Some suitable examples of top sheet materials include films, nonwovens, and laminate structures having film / nonwoven layers, film / film layers, and nonwoven / nonwoven layers.

[0083] Non-limiting examples of nonwoven web materials that may be suitable for use as topsheet 110 include fibrous materials made from natural fibers, modified natural fibers, synthetic fibers, or combinations thereof. Some suitable examples are described in U.S. Pat. Nos. 4,950,264, 4,988,344, 4,988,345, 3,978,185, 7,785,690, 7,838,099, 5,792,404, and 5,665,452.

[0084] The top sheet 110 can be compliant, feel soft, and non-irritating to the wearer's skin. In addition, the top sheet 110 can also be liquid permeable, thereby allowing liquid (e.g., urine, menstrual fluid) to easily penetrate its thickness. Some suitable examples of top sheet materials include films, nonwovens, and laminate structures with film / nonwoven layers, films / film layers, and nonwoven / nonwoven layers. Other exemplary top sheet materials and designs are disclosed in U.S. Patent Application Publications 2016 / 0129661, 2016 / 0167334, and 2016 / 0278986.

[0085] In some examples, top sheet 110 may include tufts, such as described in US 8,728,049, US 7,553,532, US 7,172,801, US 8,440,286, US 7,648,752, and US 7,410,683. Top sheet 20 may have a pattern of discrete hair-like fibrils such as described in US 7,655,176 or US 7,402,723. Additional examples of suitable top sheet materials include those described in US 8,614,365, US 8,704,036, US 6,025,535, and U.S. Patent Publication No. 2015 / 041640. Another suitable top sheet may be formed by a three-dimensional substrate, such as described in detail in US 2017 / 0258647. The topsheet may have one or more layers as described in U.S. Patent Publication Nos. 2016 / 0167334; US 2016 / 0166443 and US 2017 / 0258651.

[0086] In some examples, the top sheet 110 can be formed of a nonwoven web material of a spunbond web, the spunbond web comprising a monocomponent continuous fiber, or alternatively, a bicomponent or multicomponent fiber, or a blend of monocomponent fibers spun from different polymer resins, or any combination thereof. The top sheet can also be a formed nonwoven top sheet, as disclosed in U.S. Patent Publication No. 2019 / 0380887.

[0087] In order to ensure that the fluid contacting the top (wearer-facing) surface of the top sheet will move appropriately and quickly in the z direction to the bottom (outward-facing) surface of the top sheet, where the fluid can be sucked into the absorbent article, it is important to ensure that the nonwoven web material forming the top sheet has an appropriate weight / volume density, thereby reflecting the appropriate presence of interstitial channels (sometimes referred to as "pores") among and between the constituent fibers, through which the fluid can move in the nonwoven material. In some cases, the nonwoven material with fibers that are too densely consolidated may have pores of insufficient number and / or volume and / or size, and the nonwoven material will block rather than promote the rapid downward fluid movement in the z direction. On the other hand, the nonwoven material with fibers that are too large and / or consolidated to provide a certain degree of opacity (for the purpose of hiding the absorbed fluid in the layer below) and a significant appearance may be perceived negatively by the user.

[0088] The thickness of the topsheet material can be controlled to balance the competing demands for opacity and bulk (which require higher thickness) with the limitation of the z-direction distance that discharged fluid can travel from the wearer-facing surface through the topsheet to the outward-facing surface to reach the absorbent core component below. Therefore, it may be desirable to control the manufacture of the topsheet material to produce a topsheet material having a thickness of about 0.20 mm to about 1.0 mm, or about 0.25 mm to about 0.80 mm, or about 0.30 mm to about 0.60 mm.

[0089] Second top sheet (STS)

[0090] In some cases, an STS layer may be included between the topsheet and the absorbent core structure to enable the absorbent core structure to easily receive a sudden discharge of fluid and, after receiving it, wick the fluid in the x and y directions to distribute the fluid over the underlying absorbent core structure.

[0091] If included, the STS can be a nonwoven fibrous structure that can include cellulosic fibers, non-cellulosic fibers (e.g., fibers spun from polymer resins), or blends thereof. To accommodate the folding and lateral gathering of the absorbent article 20 and absorbent core structure 10, as described herein, the STS can be formed of a relatively flexible (i.e., having a relatively low bending stiffness) material.

[0092] Many specific examples of suitable STS compositions and structures and their combinations with suitable topsheet compositions and structures are further described in U.S. Patent Serial Nos. 16 / 831,862, 16 / 831,854, 16 / 832,270, 16 / 831,865, 16 / 831,868, 16 / 831,870, and 16 / 831,879, and U.S. Provisional Application Serial Nos. 63 / 086,610 and 63 / 086,701. Additional suitable examples are described in US 9,504,613; US2012 / 040315; and US2019 / 0021917.

[0093] In some configurations, the absorbent article may be free of a secondary topsheet.

[0094] Negatives

[0095] Backsheet 130 can be positioned below or near the outwardly facing surface of absorbent core structure 10 and can be joined thereto by any suitable attachment method. For example, backsheet 130 can be fixed to absorbent core structure 10 by an array of separate lines, spirals or points of uniform continuous adhesive layer, patterned adhesive layer or adhesive. Additionally, attachment method can include thermal bonding, pressure bonding, ultrasonic bonding, dynamic mechanical bonding or any other suitable attachment mechanism or combination thereof. In other examples, it is conceivable that absorbent core structure 10 is not directly joined to backsheet 130.

[0096] Backsheet 130 can be impermeable or substantially impermeable to aqueous liquid (for example, urine, menstrual fluid), and can be made of thin plastic film, although other liquid impermeable flexible materials can also be used.As used herein, term "flexible" refers to compliant and easily conformable to the material of the general shape and outline of human body.Backsheet 130 can prevent or at least substantially suppress absorption and be contained in the fluid in absorbent core structure 10 to escape and arrive at the clothing article of the wearer that can contact absorbent article 20, such as underwear and outer garment.However, in some cases, backsheet 130 can be made into and / or be suitable for allowing steam to escape (that is, backsheet is made into breathable) from absorbent core structure 10, and in other cases, backsheet 130 can be made so as not to allow steam to escape (that is, it is made into impermeable).Therefore, backsheet 130 can comprise polymer film, such as the thermoplastic film of polyethylene or polypropylene. Suitable materials for backsheet 130 are, for example, thermoplastic films having a thickness of about 0.012 mm (0.5 mil) to about 0.051 mm (2.0 mil).Any suitable backsheet known in the art may be used in the present invention.

[0097] Some suitable examples of materials suitable for forming the backsheet are described in US 5,885,265, US 4,342,314 and US 4,463,045. Suitable single layer breathable backsheets for use herein include those described in GB A 2184 389, GBA 2184 390, GB A 2184 391, US 4,591,523, US 3,989,867, US 3,156,242, WO 97 / 24097, US 6,623,464, US 6,664,439 and US 6,436,508.

[0098] The backsheet 130 may have two layers: a first layer comprising a vapor permeable apertured formed film layer and a second layer comprising a breathable microporous film layer, as described in US 6,462,251. Other suitable examples of double or multilayer breathable backsheets for use herein include those described in US 3,881,489, US 4,341,216, US 4,713,068, US 4,818,600, EP 203821, EP 710 471, EP 710 472 and EP 0793 952.

[0099] Other features

[0100] In some configurations, the absorbent article 20 may be provided with an adhesive deposit to provide a mechanism for the user to adhere the absorbent article to the inside of her panties in the crotch region thereof. When the absorbent article 20 is packaged for shipping, handling, and storage prior to use, the adhesive deposit may be covered by one or more sheets of a release film or paper (not shown) that covers / shields the adhesive deposit from contact with other surfaces until the user is ready to remove the release film or paper and place the absorbent article in her panties for wear / use.

[0101] In some configurations, the absorbent article 20 may include opposing wing portions 140, 150 on each side that extend transversely beyond the longitudinal edges of the absorbent portion of the absorbent article, with a width dimension that is relatively larger than the width dimensions of the front and rear portions of the absorbent article. Wings are currently commonly provided with feminine hygiene absorbent articles. As provided, they typically have an adhesive deposit applied to their outwardly facing surface (which is facing outward before the absorbent article is placed in the user's underwear and the wings are applied). The wing portions may also include an adhesive deposit as described above, which enables the user to wrap the wing portions through the leg openings of the underwear and around its inner edges, and adhere the wing portions to the outwardly facing surface / underside of the underwear in the crotch area, thereby providing additional retention support for the absorbent article and helping to protect the underwear from soiling near its leg edges.

[0102] Test Method

[0103] Layer of interest

[0104] For any of the following methods where not all component layers of the article are tested, cryo spray may be used, if desired, to separate the layer of interest from the layers not being tested.

[0105] Fracture strain method

[0106] The force-to-displacement behavior of the sample is measured on a universal constant-rate extension test frame (a suitable instrument is MTS Alliance using TestSuite software, available from MTS Systems Corp., Eden Prairie, MN, or its equivalent) equipped with a load cell, and the measured force is within 1% to 99% of the limit of the load cell. The sample is stretched at a constant rate (mm / sec) until it breaks, and the percent strain at break is measured. All tests are conducted in a room controlled at 23°C ± 3°C and 50% ± 2% relative humidity, and the test samples are conditioned in this environment for at least 2 hours prior to testing.

[0107] The grips used to hold the test specimens are lightweight (<80 grams), vise action grips with semi-cylindrical steel to rubber coated steel gripping faces at least 40 mm wide. The grips are mounted on a universal test frame and are mounted so that they are aligned horizontally and vertically with each other.

[0108] The test specimens were prepared as follows. If necessary, the test material was obtained by cutting the test material from the absorbent article. When the test material was cut, no contamination or deformation was caused to the material layer during the process. The test specimens were cut from areas without any folds or wrinkles on the test material. The test specimens were 100 mm long (parallel to the transverse axis, or the intended transverse axis of the article) and 25.4 mm wide (parallel to the longitudinal axis, or the intended longitudinal axis of the article). In a similar manner, five replicate test specimens were prepared.

[0109] The universal test frame is prepared as follows. The initial grip-to-grip spacing distance is set to a nominal gauge length of 80 mm, and the grips are then zeroed. The test frame is programmed to move the grips closer together with an intentional relaxation of 1 mm to ensure that there is no pre-tension on the test specimen at the beginning of the test. (During this movement, the specimen will become relaxed between the grips.) Next, the grips will move apart at a relaxation rate of 1 mm / s until a relaxation preload of 0.05 N is exceeded. (At this point, the grip position signal is used to calculate sample relaxation, the adjusted gauge length, and the strain is defined as zero, 0.0). The grips will then move apart at a rate of 1 mm / s until the sample breaks or the extension limit of the instrument is exceeded.

[0110] The test was performed by inserting the test specimen into the grips so that the long axis of the specimen was parallel and centered with the movement of the grips. The test was started and force ("load") and displacement data were continuously collected at a data acquisition rate of 100 Hz.

[0111] Plot a graph of load (N) versus displacement (mm). Determine the peak load from the curve and then determine the fracture sensitivity as follows. Determine the chuck position at which the load signal decreases by 75% after reaching the peak load and record it as the final length of the specimen (Lf) to the nearest 0.01 mm. The initial length of the specimen is defined by the chuck position when the relaxation preload of 0.05 N is exceeded, and this value is recorded as the initial length of the specimen (Li) to the nearest 0.01 mm. Calculate the fracture strain percentage as follows and record it to the nearest 1%.

[0112] % Fracture strain = ((Lf-Li) / Li)*100

[0113] In a similar manner, repeat this procedure for all five replicate test specimens. Calculate the arithmetic mean of the % Strain at Break for the five replicate test specimens and report as % Strain at Break to the nearest 1%.

[0114] Wet and dry CD and MD 3-point bending method

[0115] The bending properties of the absorbent article test specimens are measured on a universal constant rate extension test frame (a suitable instrument is MTS Alliance using TestSuite software, available from MTS Systems Corp., Eden Prairie, MN, or its equivalent) equipped with a load cell, and the measured force is within 1% to 99% of the limit of the load cell. The test is performed on dry test specimens as well as wet test specimens. The intention of this method is to simulate the deformation in the xy plane produced by the wearer of the absorbent article during normal use. All tests are performed in a room controlled at 23°C ± 3°C and 50% ± 2% relative humidity.

[0116] The bottom fixture consists of two cylindrical rods of polished stainless steel with a diameter of 3.175 mm and a length of 110 mm, each with frictionless roller bearings mounted on both ends. The two rods are mounted horizontally, aligned front to back and parallel to each other, with the top radius of the rods aligned vertically and free to rotate around the diameter of the cylinder through frictionless bearings. In addition, the fixture allows the two rods to move horizontally away from each other on the track so that a gap can be set between them while maintaining their orientation. The top fixture consists of a third cylindrical rod also made of polished stainless steel with a diameter of 3.175 mm and a length of 110 mm, with frictionless roller bearings mounted on both ends. When in position, the rods of the top fixture are parallel to and aligned front to back with the rods of the bottom fixture, and centered between the rods of the bottom fixture. Both fixtures include an integral adapter that is suitable for mounting in corresponding positions on a universal test frame and locking into position so that the rods are orthogonal to the movement of the test frame crossbar.

[0117] The gap between the bars of the lower fixture ("span") was set to 25 mm ± 0.5 mm (center of bar to center of bar), with the upper bar centered at the midpoint between the lower bars. The gauge length (bottom of the top bar to top of the lower bar) was set to 1.0 cm.

[0118] The thickness of the test specimens ("caliper") was measured using a manually operated micrometer equipped with a pressure gauge capable of applying 0.1 psi + 0.01 psi steady pressure on the pressure foot. This manually operated micrometer is a deadweight instrument that reads to the nearest 0.01 mm. A suitable instrument is the Mitutoyo Series 543ID-C Digimatic, available from VWR International, or equivalent. The pressure foot is a flat circular movable surface not greater than 25.4 mm in diameter. The test specimen is supported by a horizontal flat reference platform that is larger than and parallel to the surface of the pressure foot. Zero the micrometer against the horizontal flat reference platform. Place the test specimen on the platform, centered under the pressure foot. Adjust the pressure foot by hand at 3 + The pressure foot is lowered at a rate of 1 mm / s until the full weight of the pressure is applied to the specimen. After 5 seconds have elapsed, the thickness is recorded as the caliper to the nearest 0.01 mm.

[0119] Prepare the test fluid for metering the wet test specimens by adding 100.0 grams of sodium chloride (reagent grade, any convenient source) to 900 grams of deionized water in a 1 liter Erlenmeyer flask. Stir until the sodium chloride is completely dissolved.

[0120] Prior to testing, condition the absorbent article at 23°C ± 3°C and 50% ± 2% relative humidity for two hours. The dry test specimen is taken from a sample area free of any seams and creases or wrinkles, and is ideally taken from the center of the absorbent article (the intersection of the longitudinal and transverse centerlines). Prepare the dry specimen for MD (longitudinal) bending in the following manner: cut the dry specimen into a width of 50.8 mm along the CD (transverse; parallel to the transverse axis of the sample) and a length of 50.8 mm along the MD (parallel to the longitudinal axis of the sample), keep their orientation after cutting, and mark the surface facing the body (or the surface intended to face the finished body). Prepare the dry specimen for CD (longitudinal) bending in the following manner: cut the dry specimen into a width of 50.8 mm along the MD (transverse; parallel to the transverse axis of the sample) and a length of 50.8 mm along the CD (parallel to the longitudinal axis of the sample), keep their orientation after cutting, and mark the surface facing the body (or the surface intended to face the finished body). Measure the thickness of the test specimen as described herein and record it as the dry specimen thickness to the nearest 0.01 mm. Now measure the mass of the test specimen and record it as the dry mass to the nearest 0.001 gram. Calculate the mass (g) by dividing the area (0.002581 m 2 ) to calculate the basis weight of the sample and record it as the dry sample basis weight, accurate to 0.01 g / m 2 By changing the sample basis weight (g / m 2 ) divided by the sample thickness (mm), then divided the quotient by 1000 to calculate the bulk density of the sample and record it as the dry sample density to the nearest 0.01 g / cm 3 In a similar manner, five replicate dry test specimens were prepared.

[0121] The wet test specimen is initially prepared in exactly the same manner as the dry test specimen, and then the test fluid is added just before the test, as described below. First, the thickness and mass of the dry specimen are measured as described herein, and recorded as the initial thickness (accurate to 0.01mm) and the initial mass (accurate to 0.001g). Next, the dry specimen is completely immersed in the test fluid for 60 seconds. After 60 seconds have passed, the specimen is removed from the test fluid and vertically oriented for 30 seconds to allow any excess fluid to drip. As described herein, the thickness and mass of the wet specimen are now measured, and recorded as the wet specimen thickness (accurate to 0.01mm) and the wet specimen mass (accurate to 0.001g). If necessary, the mass of the test fluid in the test specimen is calculated by subtracting the initial mass (g) from the wet specimen mass (g) and recording it as the test specimen fluid amount (accurate to 0.001g). After removing the wet test specimen from the test fluid, it must be tested within 10 minutes. In a similar manner, five repeated wet test specimens were prepared.

[0122] The universal test frame for flexural bend testing was programmed to move the grips so that the top fixture moved downward relative to the lower fixture at a rate of 1.0 mm / s until the upper rod contacted the top surface of the specimen with a nominal force of 0.02 N and then continued for an additional 12 mm. The grips were then immediately returned to the original gauge length at a rate of 1.0 mm / s. Force (N) and displacement (mm) data were collected continuously at 100 Hz throughout the test.

[0123] Load the dry test specimen so that it spans the two bottom bars and is centered under the top bar with its sides parallel to the bars. For MD bending, the MD direction of the specimen is perpendicular to the length of the 3 bars. Start the test and continuously collect force and displacement data.

[0124] Plot force (N) versus displacement (mm). From the graph determine the maximum peak force and record it as the Dry MD Peak Load to the nearest 0.01 N. Now calculate the maximum slope of the curve between the initial force and the maximum force (during the loading portion of the curve) and record it to the nearest 0.1 unit. Calculate the modulus as follows and record it as the Dry MD Modulus to the nearest 0.001 N / mm 2 .

[0125] CD or MD dry or wet flexural modulus (N / mm 2 )=(slope×(span 3 )) / (4×sample width×(sample thickness 3 ))

[0126] Calculate the bending stiffness as follows and record it as dry MD bending stiffness to the nearest 0.1 N mm 2 .

[0127] CD or MD dry or wet bending stiffness (N mm 2 ) = modulus × moment of inertia where moment of inertia (mm 4 )=(specimen width×(specimen thickness 3 )) / 12

[0128] In a similar manner, repeat the procedure for all five replicate dry test samples. The arithmetic mean between the five replicate dry test specimens is calculated for each of the parameters and reported as dry specimen "thickness" (accurate to 0.01 mm), dry specimen basis weight (accurate to 0.01 g / m 2 ), dry sample density (accurate to 0.001g / cm 3 ), dry CD or MD peak load (accurate to 0.01N), dry CD or MD flexural modulus (accurate to 0.001N / mm 2 ) and dry CD or MD bending stiffness (accurate to N mm 2 ).

[0129] The entire procedure is now repeated for all five replicates of the wet test specimens and the results are reported as wet CD or MD peak load (to the nearest 0.01 N), wet CD or MD flexural modulus (to the nearest 0.001 N / mm 2 ) and wet CD or MD bending stiffness (accurate to N mm 2 ).

[0130] Wet and dry CD ultra-sensitive 3-point bending method

[0131] The CD (cross direction) bending properties of the test specimens are measured using an ultra-sensitive 3-point bend test on a universal constant rate extension test frame (a suitable instrument is MTS Alliance using TestSuite software, available from MTS Systems Corp., Eden Prairie, MN, or its equivalent) equipped with a load cell suitable for measuring force. The test is performed on dry test specimens as well as wet test specimens. The intent of this method is to simulate the deformation in the xy plane produced by the wearer of the absorbent article during normal use. All tests are performed in a room controlled at 23°C ± 3°C and 50% ± 2% relative humidity.

[0132] The ultra-sensitive 3-point bend method is designed to maximize the force signal-to-noise ratio when testing materials with very low bending forces. The force signal is maximized by using a highly sensitive load cell (e.g. 5N), using a small span (the load is proportional to the cube of the span), and using a wide specimen width (the total load measured is proportional to the width). The fixture is designed so that the bend measurement is made under tension, allowing the fixture mass to be kept to a minimum. The noise in the force signal is minimized by keeping the load cell stationary to reduce mechanical vibration and inertial effects, and by keeping the mass of the fixture attached to the load cell as low as possible.

[0133] See also 7A to 7C, load sensor 1001 is mounted on the fixed clamp of the universal test frame. The ultra-sensitive fixture 1000 consists of three thin blades made of a lightweight rigid material (such as aluminum or equivalent). Each blade has a thickness of 1.0mm, rounded edges and a length that can accommodate a bending width of 100mm. Each of the blades has cavities 1004a and 1004b (outer blades) and 1005 (center blade), which are cut out to form blade material with a height h of 5mm along its horizontal edges. The two outer blades 1003a and 1003b are horizontally mounted to the movable clamp of the universal test frame, aligned parallel to each other, and their horizontal edges are vertically aligned. The span s between the two outer blades 1003a and 1003b is 5mm±0.1mm (inner edge to inner edge). The center blade 1002 is mounted to the load sensor on the fixed clamp of the universal test frame. When in position, the center blade 1002 is parallel to the two outer blades 1003a and 1003b and is centered at the midpoint between the outer blades 1003a and 1003b. The blade fixture includes integral adapters that are adapted to be mounted in corresponding locations on the universal test frame and locked into position so that the horizontal edge of the blade is orthogonal to the motion of the universal test frame crossbar.

[0134] Prepare the test fluid for metering the wet test specimens by adding 100.0 grams of sodium chloride (reagent grade, any convenient source) to 900 grams of deionized water in a 1 liter Erlenmeyer flask. Stir until the sodium chloride is completely dissolved.

[0135] Prior to testing, the samples were conditioned at 23°C ± 3°C and 50% ± 2% relative humidity for two hours. Dry test specimens were taken from sample areas where no seams and creases or wrinkles remained. Dry specimens were prepared for CD bending (i.e., bending perpendicular to the transverse axis of the sample) in the following manner: the dry specimens were cut into a width of 50.0 mm along the CD (transverse; parallel to the transverse axis of the sample) and a length of 100.0 mm along the MD (longitudinal; parallel to the longitudinal axis of the sample), maintaining their orientation after cutting, and marking the body-facing surface (or the surface intended to face the finished body). In a similar manner, five repeated dry test specimens were prepared.

[0136] The wet test specimens were initially prepared in exactly the same manner as the dry test specimens, followed by the addition of the test fluid just prior to testing, as described below. The dry specimens were completely immersed in the test fluid for 60 seconds. After the 60 seconds had elapsed, the specimens were removed from the test fluid and oriented vertically for 30 seconds to allow any excess fluid to drip off. After the wet test specimens were removed from the test fluid, the test must be performed within 10 minutes. In a similar manner, five replicate wet test specimens were prepared.

[0137] The universal test frame was programmed so that the movable chuck was set to move in a direction opposite to the fixed chuck at a rate of 1.0 mm / s. The chuck movement began with the specimen 1006 lying flat on the outer blades 1003a and 1003b and not deflected, continued as the inner horizontal edge of the cavity 1005 in the center blade 1002 contacted the top surface of the specimen 1006, and further continued with an additional 4 mm of chuck movement. The chuck stopped at 4 mm and then immediately returned to zero at a rate of 1.0 mm / s. Force (N) and displacement (mm) were collected at 50 Hz throughout the process.

[0138] Prior to loading the test specimen 1006, the outer vanes 1003a and 1003b are moved toward the center vane 1002 and then past the center vane until a gap C of approximately 3 mm exists between the inner horizontal edges of the cavities 1004a and 1004b in the outer vanes 1003a and 1003b and the inner horizontal edge of the cavity 1005 in the center vane 1002 (see Figure 7C ). Sample 1006 is placed in gap C so that it spans the inner horizontal edges of cavities 1004a and 1004b in outer leaves 1003a and 1003b, oriented so that the MD (short edge) of the sample is perpendicular to the horizontal edges of the leaves and the body-facing surface of the sample faces upward. Center sample 1006 between outer leaves 1003a and 1003b. Slowly move outer leaves 1003a and 1003b in a direction opposite to the fixed chuck until the inner horizontal edge of cavity 1005 in center leaf 1002 contacts the top surface of sample 1006. Start testing and continuously collect force and displacement data.

[0139] Force (N) versus displacement (mm) is plotted. The maximum peak force is recorded to the nearest 0.001 N. The area under the curve from the start of loading until the maximum peak force is calculated and recorded as the bending energy to the nearest 0.001 N-mm. The recovery energy is calculated as the area under the curve where the force is unloaded from the maximum peak to 0.0 N, and the recovery energy is recorded to the nearest 0.001 N-mm. In a similar manner, the entire test sequence is repeated for a total of five dry test specimens and five wet test specimens.

[0140] For each test specimen type (dry and wet), calculate the arithmetic mean of the maximum peak force among similar specimens to the nearest 0.001 N and report as Dry Peak Load and Wet Peak Load, respectively. For each test specimen type (dry and wet), calculate the arithmetic mean of the bending energy among similar specimens to the nearest 0.001 N-mm and report as Dry Bend Energy and Wet Bend Energy, respectively. For each test specimen type (dry and wet), calculate the arithmetic mean of the recovery energy among similar specimens to the nearest 0.001 N-mm and report as Dry Recovery Energy and Wet Recovery Energy, respectively.

[0141] Wet and dry push-up compression methods

[0142] The Gathered Compression Test Method measures the force-to-displacement behavior of an intentionally "gathered" absorbent article test sample over five cycles of load application ("compression") and load removal ("recovery") using a universal constant-rate extension test frame equipped with a load cell (a suitable instrument is MTS Alliance using TestSuite software, available from MTS Systems Corp., Eden Prairie, MN, or its equivalent), the forces measured being within 1% to 99% of the limits of the load cell. The test is conducted on dry test specimens as well as wet test specimens metered with a specified amount of test fluid. The intent of this method is to simulate the deformations produced in the z-plane of the crotch region of an absorbent article or component thereof when worn by a wearer during sit-stand exercise. All tests are conducted in a room controlled at 23°C ± 3°C and 50% ± 2% relative humidity.

[0143] Test equipment in Figures 8 to 9B Depicted in . The bottom fixed fixture 3000 consists of two matching sample clamps 3001, each clamp is 100mm wide, each clamp is mounted on its own movable platform 3002a, 3002b. The clamps have a 110mm long "blade" 3009, which rests against a 1mm thick hard rubber surface 3008. When closed, the clamps are flush with the inside of their corresponding platforms. The clamps are aligned so that they hold the unassembled specimens horizontally and orthogonal to the pulling axis of the tensile tester. The platforms are mounted on guide rails 3003, which allow them to be moved horizontally from left to right and locked in place. The guide rails have adapters 3004 compatible with the brackets of the tensile tester, which can fix the platforms horizontally and orthogonally to the pulling axis of the tensile tester. The upper fixture 2000 is a cylindrical plunger 2001, which has an overall length of 70mm and a diameter of 25.0mm. The contact surface 2002 is flat, without curvature. The plunger 2001 has an adapter 2003 compatible with the bracket of the load cell, which enables the plunger to be fixed orthogonally to the pulling axis of the tensile tester.

[0144] Before testing, the test sample is conditioned at 23°C ± 3°C and 50% ± 2% relative humidity for at least 2 hours. Prepare the test specimen as follows. When testing a complete absorbent article, remove the release paper (if present) from any panty adhesive on the garment-facing side of the article. Apply talcum powder lightly to the adhesive to relieve any stickiness. If there is a hoop, cut them off with scissors so as not to interfere with the top sheet or any other underlying layer of the article. The article is placed on a workbench in a manner facing the body surface upward. Mark the intersection of the longitudinal centerline and the transverse centerline on the article. Use a rectangular punching die or equivalent cutting device to cut out a sample of 100mm in the longitudinal direction by 80mm in the transverse direction, with its center located at the intersection of the centerline. When testing the material layer or layered component of the absorbent article, place the material layer or layered component on the workbench and orient it to be integrated into the finished product, that is, identify the surface facing the body and the transverse and longitudinal axes. Use a rectangular punching die or equivalent cutting device to cut out a sample of 100mm in the longitudinal direction by 80mm in the transverse direction, with its center located at the intersection of the centerline. Measure the mass of the sample and record it to the nearest 0.001 gram. Divide the mass (g) by the area (0.008 m 2 ) to calculate the basis weight of the sample and record it as basis weight, accurate to 1g / m 2 .

[0145] The specimens can be analyzed both wet and dry. No further preparation is required for dry specimens. Prepare the test fluid for metering the wet test specimens by adding 100.0 grams of sodium chloride (reagent grade, any convenient source) to 900 grams of deionized water in a 1 liter conical flask. Stir until the sodium chloride is completely dissolved. A total of 7 ml of test solution is metered into the wet specimens as detailed below.

[0146] A calibrated Eppendorf-type pipette was used to add the liquid dose, spreading the fluid over the entire body-facing surface of the specimen over a period of approximately 3 seconds. The wet specimen was tested 10.0 min ± 0.1 min after the dose was applied.

[0147] The tensile tester is programmed to zero the load cell and then lower the upper clamp at a rate of 2.00 mm / sec until the contact surface of the plunger contacts the specimen and the reading at the load cell is 0.02 N. Zero the chuck. The system is programmed to lower the chuck by 15.00 mm at a rate of 2.00 mm / sec and then immediately raise the chuck by 15.00 mm at a rate of 2.00 mm / sec. Repeat this cycle for a total of five cycles with no delay between cycles. Data is collected at a frequency of 50 Hz during all compression / decompression cycles.

[0148] Position the left platform 3002a 2.5 mm (distance 3005) from the side of the upper plunger. Lock the left platform in place. This platform 3002a will remain fixed throughout the experiment. Align the right platform 3002b 50.0 mm (distance 3006) from the fixed clamp. Raise the upper probe 2001 so that it will not interfere with the loading of the specimen. Open both clamps 3001. See Fig.9A , place the dry specimen in the fixture with its longitudinal edge (i.e., the 100 mm long edge). With the dry specimen centered transversely, securely fasten both edges in the fixture. Fig. 9B , move the right platform 3002b towards the fixed platform 3002a by a distance of 20 mm so that a spacing of 30.0 mm is achieved between the left and right clamps. When positioning the movable platform, allow the dry specimen to bend upward. Now manually lower the probe 2001 until the bottom surface is approximately 1 cm above the top of the bent specimen.

[0149] The test was started and force (N) versus displacement (mm) data was continuously collected for all five cycles. A graph of force (N) versus displacement (mm) was plotted separately for all cycles. A representative curve is shown in Fig. 10A From this curve, determine the dry maximum compressive force for each cycle to the nearest 0.01 N, then multiply by 101.97 and record to the nearest 1 gram-force. Calculate the "% Dry Recovery" between the "First Cycle" and the "Second Cycle" as (TD-E2) / (TD-E1)*100 and record to the nearest 0.01%, where TD is the total displacement and E2 is the elongation on the second compression curve that exceeds 0.02 N. In a similar manner, calculate the % Dry Recovery between the first cycle and the additional cycles as (TD-E1) / (TD-E1)*100 and record to the nearest 0.01%. See Fig. 10B , the dry compression energy of cycle 1 is calculated as the area under the compression curve (i.e., Area A+B) and recorded to the nearest 0.1 N-mm. The dry energy loss of cycle 1 is calculated as the area between the compression and decompression curves (i.e., Area A) and recorded to the nearest 0.1 N-mm. The dry recovery energy of cycle 1 is calculated as the area under the decompression curve (i.e., Area B) and reported to the nearest 0.1 N-mm. The dry compression energy (N-mm), dry energy loss (N-mm), and dry recovery energy (N-mm) of each of the other cycles are calculated in a similar manner and recorded to the nearest 0.1 N-mm. In a similar manner, a total of five repeated dry test specimens are analyzed, and the arithmetic mean between the five dry repeats of each parameter (including basis weight) as described above is reported.

[0150] Now repeat the entire procedure for a total of five replicate wet test specimens, reporting the results for each of the five cycles as the arithmetic mean of the five wet replicates for the following: Wet Maximum Compressive Force (to the nearest 1 gram-force) per cycle, Wet Compressive Energy (to the nearest 0.1 N-mm) per cycle, Wet Energy Loss (to the nearest 0.1 N-mm) per cycle, Wet Recovery Energy (to the nearest 0.1 N-mm) per cycle, and Wet Recovery % per cycle. Of particular importance are the Fifth Cycle Wet Recovery Energy and Fifth Cycle Wet Recovery % properties from this test method.

[0151] CD cyclic elongation to 3% strain

[0152] Cyclic stretch and recovery response of absorbent article specimens is measured using a universal constant rate extension test frame for ten cycles of sustained load application ("elongation") and load removal ("recovery"). The test specimen is cycled ten times to 3% engineering strain and then returned to zero engineering strain. For each cycle, stiffness, peak load, normalized peak energy, normalized recovery energy, strain at the beginning of the cycle, and strain at the end of the cycle (i.e., "permanent strain") are calculated and reported. The intent of this method is to understand the ability of a sample to stretch in the xy plane due to body forces and then return to its original state. All measurements are performed in a laboratory maintained at 23°C ± 2°C and 50% ± 2% relative humidity, and the specimens are conditioned in this environment for at least 2 hours prior to testing.

[0153] A suitable universal constant rate extension test frame is an MTS Alliance interfaced with a computer running TestSuite control software (available from MTS Systems Corp, Eden Prairie, MN), or equivalent. The universal test frame is equipped with a load cell, the forces measured being within 1% to 99% of the load cell's limit. The fixtures used to grip the test specimens are lightweight (<80 grams), vise-action fixtures with knife or serrated edge gripping faces at least 40 mm wide. The fixtures are mounted on the universal test frame and are mounted so that they are aligned horizontally and vertically with each other.

[0154] The test specimens are prepared as follows. If necessary, the test material is obtained by cutting the test material from the absorbent article. When cutting the test material, no contamination or deformation of the material layer is caused during the process. The test specimen is cut from an area of ​​the test material without any residual creases or wrinkles. The test specimen is as long as the transverse length of the article (parallel to the transverse axis of the article, or the intended transverse axis of the article). When cutting specimens from absorbent articles of different sizes and widths, the total specimen length (L 总计) may vary from product to product, so the results will be normalized to compensate for this variation. The test specimen has a width of 25.4 mm (parallel to the longitudinal axis or intended longitudinal axis of the article). Specimen width (w) = 25.4 mm. Measure and record the total specimen length (L 总计 ), accurate to 0.1 mm. In a similar manner, five repeated test specimens were prepared.

[0155] The thickness (t) of the test specimens was measured using a manually operated micrometer equipped with a pressure gauge capable of applying 0.1 psi + 0.01 psi steady pressure on the pressure foot. This manually operated micrometer is a deadweight instrument that reads to the nearest 0.01 mm. A suitable instrument is the Mitutoyo Series 543ID-C Digimatic, available from VWR International, or equivalent. The pressure foot is a flat circular movable surface not greater than 25.4 mm in diameter. The test specimen is supported by a horizontal flat reference platform that is larger than and parallel to the surface of the pressure foot. Zero the micrometer against the horizontal flat reference platform. Place the test specimen on the platform, centered under the pressure foot. Adjust the pressure foot by hand at 3 + Lower the pressure foot at a rate of 1 mm / s until the full weight of the pressure is applied to the specimen. After 5 seconds have passed, record the thickness as the specimen thickness (t) to the nearest 0.01 mm.

[0156] Prepare the universal test frame as follows. Set the initial grip-to-grip separation distance to a nominal gauge length (L) that is shorter than the total specimen length. 标称 ) and allows the specimen to be securely clamped at both ends (i.e., L 标称 <L 总计 ). The grips are then zeroed. The test frame is programmed to move the grips closer together with an intentional slack of 1 mm to ensure that no pre-tension is present on the test specimen at the start of the test. (During this movement, the specimen will become relaxed between the tension grips.) Next, the grips will move apart at a relaxation rate of 1 mm / s until a relaxation preload of 0.05 N is exceeded. At this point, the following holds. 1) The grip position signal (mm) is defined as the specimen relaxation (L 松弛 ). 2) Calculate the initial specimen gauge length (L0) as the nominal gauge length plus the relaxation L0 = L 标称 +L 松弛, where the units are in millimeters. 3) The clamp extension (ΔL) is set to zero (0.0mm). 4) The clamp displacement (mm) is set to zero (0.0mm). At this position, the engineering strain is zero, 0.0. Engineering strain is calculated as the change in length (ΔL) divided by the initial length (L0). Engineering strain = ΔL / L0. For one test cycle, the clamps are moved apart at an initial speed of 1mm / s until the engineering strain endpoint of 0.03mm / mm is exceeded, followed by the clamps moving toward each other at an initial speed of 1mm / s until the clamp signal becomes less than the clamp return position of 0mm. This test cycle is repeated until a total of 10 cycles are completed.

[0157] The test was performed by inserting the test specimen into the grips so that the long axis of the specimen was parallel and centered with the movement of the grips. The test was started and time, force and displacement data were continuously collected at a data acquisition rate of 100 Hz.

[0158] For all ten cycles, plot force (N) versus displacement (mm). For each cycle, do the following. Record the peak load to the nearest 0.01N. Calculate the peak energy (E 峰值 ), as the area under the load versus displacement curve from the start of the cycle to the strain endpoint of 0.03 mm / mm (during the loading portion of the cycle), and recorded to the nearest 0.01 N*mm. Calculate the return energy (E 返回 ) is taken as the area under the load versus displacement curve from the strain endpoint of 0.03 mm / mm to the chuck return of 0 mm (during the unloading portion of the cycle) and is recorded as the recovery energy to the nearest 0.01 N*mm. The normalized peak energy (NE 峰值 ) is calculated as the peak energy divided by the initial length, where NE 峰值 =E 峰值 / L0 and record it to the nearest 0.01mN. 返回 ) is calculated as the returned energy divided by the initial length (NE 返回 =E 返回 / L0) and record it to the nearest 0.01mN. 峰值 and NE 返回 The unit is millinewton (mN).

[0159] Now plot the engineering stress (σ) versus engineering strain for all ten cycles and for each cycle do the following. 2Engineering stress in units is the load divided by the cross-sectional area of ​​the specimen, where the cross-sectional area is the specimen width (w) multiplied by the thickness (t), σ = load / (w * t). The modulus or the slope of the stress-strain curve is determined for the line between the point occurring at the minimum force and the point occurring at the maximum force (during the loading portion of the cycle) and recorded as the modulus, accurate to 0.01 N / mm. Stiffness is calculated by multiplying the modulus by the specimen thickness and recorded as tensile stiffness, accurate to 0.01 N / mm. The strain of the test specimen at the beginning of the cycle is defined as the strain when the cycle exceeds a relaxed preload of 0.05 N (during the loading portion of the cycle) and is recorded as the initial strain of the cycle, accurate to 0.01 mm / mm. The strain of the test specimen at the end of the cycle is defined as the strain when the load becomes less than the preload of 0.05 N of the cycle (during the unloading portion of the cycle) and is recorded as the permanent strain, accurate to 0.01 mm / mm. In a similar manner, the entire procedure is now repeated for all five repetitions.

[0160] For each of the ten cycles, the arithmetic mean of the five replicate test specimens is calculated for each of the parameters and reported as peak load (accurate to 0.01N), normalized peak energy (accurate to 0.01mN), normalized recovery energy (accurate to 0.01mN), tensile stiffness (accurate to 0.01N / mm), cycle initial strain (accurate to 0.01mm / mm) and permanent strain (accurate to 0.01mm / mm).

[0161] Method for measuring pattern spacing and area of ​​structural bonding areas

[0162] On the image of the absorbent article sample collected using a flatbed scanner, the spacing between the discrete structural bonding sites used to produce a quilted pattern on the absorbent article sample, and the total area occupied by the sum of these elements in the specified area of ​​the sample are measured. The scanner can scan in reflective mode with a resolution of 2400dpi and 8-bit grayscale. A suitable scanner is an Epson Perfection V750 Pro from Epson America Inc., Long Beach CA, or an equivalent. The scanner interacts with a computer running an image analysis program. A suitable program is ImageJ v.1.52, National Institute of Health, USA, or an equivalent. The sample image is distance calibrated according to the image collected by the NIST-verified straight ruler. In order to achieve maximum contrast, the sample is backed with an opaque black background of uniform color before the image is collected. All tests are carried out in a conditioning room maintained at about 23 ± 2°C and about 50 ± 2% relative humidity.

[0163] Each test sample is prepared as follows. The absorbent article is removed from any wrapping paper present. If the article is folded, it is gently unfolded and any wrinkles are smoothed. If wings are present, they are extended but the release paper remains intact. Prior to testing, the test samples are conditioned for 2 hours at a temperature of about 23°C ± 2°C and about 50% ± 2% relative humidity.

[0164] The image is obtained as follows. A ruler is placed on the scanning bed so that it is oriented parallel to the side of the scanner glass. An image of the ruler (calibration image) is collected in reflection mode at a resolution of 2400dpi (approximately 94 pixels / mm) and 8-bit grayscale. The calibration image is saved as an uncompressed TIFF format file. After obtaining the calibration image, the ruler is removed from the scanner glass and the test sample is scanned as follows under the same scanning conditions. The test sample is placed on the center of the scanner glass and fixed, if necessary, so that it lies flat, wherein the body-facing surface of the sample faces the glass surface of the scanner. The sample is oriented in a manner that the entire sample is within the glass surface. A black background is placed on top of the sample, the scanner lid is closed, and a scanned image of the entire sample is collected with the same settings as those used for the calibration image. The sample image is saved as an uncompressed TIFF format file.

[0165] Analyze the test sample image as follows. Open the calibration image file in the image analysis program and calibrate the image resolution using an imaging ruler to determine the number of pixels per millimeter. Now open the sample image in the image analysis program and set the distance scale using the image resolution determined from the calibration image. Now visually inspect the pattern of embossed elements present on the sample in the image and identify the pattern area to be analyzed. For example, the absorbent article can be divided into three zones of equal length in the longitudinal direction, such as the front third (Zone 1), the center third (Zone 2), and the end third (Zone 3). Use the image analysis tool to draw a shape along the outer perimeter of the first discrete area to be analyzed. Measure the area of ​​this first area and record it as the total area of ​​Zone 1 to the nearest 0.01mm 2 . Now measure the area of ​​each individual, discrete embossed element located inside the perimeter of Zone 1 as follows. Draw a minimum bounding circle around the individual embossed element so that no part of the embossed element lies outside the bounding circle. Now measure the area of ​​the bounding circle for that embossed element and record the embossed element area to the nearest 0.01 mm 2 In a similar manner, measure the area of ​​each embossed element, including the portion of the embossed element that is within Zone 1, and record each to the nearest 0.01 mm. 2 Now add up the areas of all embossed elements in zone 1 and record this as the total embossed element area for zone 1 to the nearest 0.01 mm. 2. Divide the total embossed element area of ​​Zone 1 by the total area of ​​Zone 1, then multiply by 100 and record as the % of the total area of ​​Zone 1 occupied by the embossed elements. The spacing between each discrete embossed element within Zone 1 is measured as follows. As described herein, measure the distance from the center of the smallest bounding circle drawn around the discrete embossed elements within Zone 1 to the center of the smallest bounding circle drawn around the nearest adjacent discrete embossed element within Zone 1 and record that distance as the embossed spacing, accurate to 0.01 mm. Repeat in a similar manner for all adjacent embossed elements within Zone 1 and record each distance, accurate to 0.01 mm. Now calculate the arithmetic mean between all measured embossing spacings measured between the nearest neighbors within Zone 1 and record as the Zone 1 embossing spacing, accurate to 0.01 mm.

[0166] In a similar manner, the entire procedure is repeated for each additional zone containing embossed elements present on the test sample and labeled accordingly as Zone 2, Zone 3, etc.

[0167] Light touch rewetting

[0168] The touch rewet method is a method of quantitatively measuring the mass of liquid that flows from an absorbent article test sample to which a specified volume of artificial menstrual fluid (AMF; as described herein) has been metered when a weight is applied for a specified length of time. All tests were conducted in a laboratory maintained at 23°C ± 2°C and 50% ± 2% relative humidity.

[0169] Use a syringe pump equipped with a disposable syringe to meter the test sample. A suitable pump is Compact S (available from B. Braun) or equivalent, and must be able to accurately dispense AMF at a rate of 42 ml / min. A disposable syringe of sufficient volume (e.g., BD Plastipak 20 mL) connected to a flexible tube with an inner diameter of 3 / 16" (e.g., Original Tubing, purchased from Brau, or equivalent). AMF was prepared as described herein and allowed to reach room temperature (23°C ± 2°C) before use in this test. Before starting the measurement, the syringe was filled with AMF and the flexible tubing was primed with liquid, and the dispensing rate (42 ml / min) and metering volume (4.0 mL) were verified according to the manufacturer's instructions. + 0.05 mL). The flexible tube was then installed so that it was oriented vertically above the test sample and the distance between the tip of the tube and the test sample surface was 19 mm. Note that the AMF must be removed from the syringe every 15 minutes and mixed thoroughly.

[0170] The rewetting weight assembly consists of an acrylic plate and a stainless steel weight. The acrylic plate has dimensions of 65 mm x 80 mm and a thickness of approximately 5 mm. The stainless steel weight together with the acrylic plate has a combined mass of 2 pounds (907.19 g) to apply a pressure of 0.25 psi below the surface of the acrylic plate.

[0171] For each test sample, five pieces of filter paper measuring 4 inches by 4 inches were used as the rewetting substrate. Prior to testing, the filter paper was conditioned at 23°C ± 2°C and 50% ± 2% relative humidity for at least 2 hours. Suitable filter paper has a basis weight of about 139 gsm, a thickness of about 700 microns, has an absorption rate of about 1.7 seconds, and is available from Ahlstrom-Munksjo North America LLC, Alpharetta, GA VWR International as Ahlstrom grade 989 or equivalent.

[0172] Prepare the test samples according to the following steps. Before testing, condition the test samples at 23°C ± 2°C and 50% ± 2% relative humidity for at least 2 hours. Remove the test samples from all packaging, being careful not to press or pull the product when handling. Place the test sample on a horizontal rigid flat surface and gently flatten any creases. Determine the test position as follows. For symmetrical samples (i.e., when the midpoint of the longitudinal axis of the sample is divided laterally, the front of the sample has the same shape and size as the back of the sample), the test position is the intersection of the midpoint of the longitudinal axis of the sample and the midpoint of the transverse axis. For asymmetrical samples (i.e., when the midpoint of the longitudinal axis of the sample is divided laterally, the front of the sample does not have the same shape and size as the back of the sample), the test position is the midpoint of the longitudinal axis of the sample and the intersection of the transverse axis located at the midpoint of the sample wing. Prepare a total of three test samples.

[0173] The test sample is placed on a horizontal flat rigid surface, where the previously identified test position is centered directly below the tip of the flexible tube. The height of the tube is adjusted so that it is 19.0mm above the test sample surface. The pump is started to dispense 4.0mL ± 0.05mL of AMF at a rate of 42ml / min. Once the AMF is fully dispensed, a 10-minute timer is started. The mass of 5 filter papers is now obtained and recorded as dry mass, accurate to 0.001 grams. When 10 minutes have passed, five pre-weighed filter papers are placed on the test sample, and the stack is centered on the metering position. Now an acrylic plate is placed in the center of the top of the filter paper so that the long side of the plate is parallel to the longitudinal axis of the test sample. Now carefully lower the stainless steel weight centered above the acrylic plate and immediately start the timer for 30 seconds. After 30 seconds have passed, gently remove the rewetting weight and acrylic plate and set aside. The mass of five filter papers is obtained and recorded as wet mass, accurate to 0.001 grams. Subtract the dry mass from the wet mass of the filter paper and record as the rewet to the nearest 0.001 gram. Before testing the next sample, wipe off any residual test liquid from the underside of the acrylic plate. Repeat in a similar manner for a total of three replicate test samples.

[0174] The arithmetic mean of the rewet among the three replicate test samples was calculated and reported as "Light Touch Rewet" to the nearest 0.001 g.

[0175] Artificial menstrual fluid (AMF) preparation

[0176] Artificial menstrual fluid (AMF) consists of a mixture of defibrillated sheep blood, phosphate buffered saline solution and a mucus component. AMF is prepared so that it has a viscosity between 7.15 and 8.65 centistokes at 23°C.

[0177] The viscosity of AMF is measured using a low viscosity rotational viscometer (a suitable instrument is a Cannon LV-2020 rotational viscometer with a UL adapter from Cannon Instrument Co., State College, PA, or an equivalent instrument). A spindle of appropriate size within the viscosity range is selected, and the instrument is operated and calibrated according to the manufacturer. The measurements are performed at 23°C ± 1°C and at 60rpm. Results are reported to the nearest 0.01 centistoke.

[0178] The reagents required for AMF preparation include: defibrinated sheep blood with a packed cell volume of 38% or greater (collected under sterile conditions and purchased from Cleveland Scientific, Inc., Bath, OH, or equivalent), gastric mucin with a viscosity of 3-4 centistokes when prepared as a 2% aqueous solution (crude form, sterile, purchased from American Laboratories, Inc., Omaha, NE, or equivalent), 10% v / v lactic acid in water, 10% w / v potassium hydroxide in water, disodium hydrogen phosphate (reagent grade), sodium chloride (reagent grade), sodium dihydrogen phosphate (reagent grade), and distilled water, each purchased from VWR International or equivalent source.

[0179] Phosphate buffered saline solution consists of two separately prepared solutions (Solution A and Solution B). To prepare 1 L of Solution A, add 1.38 ± 0.005 g of monobasic sodium phosphate and 8.50 ± 0.005 g of sodium chloride to a 1000 mL volumetric flask and add distilled water to the flask. Mix thoroughly. To prepare 1 L of Solution B, add 1.42 ± 0.005 g of disodium hydrogen phosphate and 8.50 ± 0.005 g of sodium chloride to a 1000 mL volumetric flask and add distilled water to the flask. Mix thoroughly. To prepare phosphate buffered saline solution, add 450 ± 10 mL of Solution B to a 1000 mL beaker and stir at low speed on a stir plate. Insert a calibrated pH probe (accurate to 0.1) into the beaker of Solution B and add enough Solution A while stirring to bring the pH to 7.2 ± 0.1.

[0180] The mucus component is a mixture of phosphate buffered saline solution, potassium hydroxide aqueous solution, gastric mucin and lactic acid aqueous solution. The amount of gastric mucin added to the mucus component directly affects the final viscosity of the prepared AMF. In order to determine the amount of gastric mucin required to obtain AMF in the target viscosity range (7.15-8.65 centistokes at 23°C), 3 batches of AMF with different amounts of gastric mucin were prepared in the mucus component, and then the exact amount required was interpolated from the concentration-viscosity curve using a three-point least squares linear fit. The successful range of gastric mucin is usually between 38 grams and 50 grams.

[0181] To prepare approximately 500 mL of the mucus fraction, 460 ± 10 mL of the previously prepared phosphate buffered saline solution and 7.5 ± 0.5 mL of a 10% w / v potassium hydroxide aqueous solution are added to a 1000 mL heavy glass beaker. The beaker is placed on a stirring hot plate and the temperature is raised to 45°C ± 5°C while stirring. A predetermined amount of gastric mucin (± 0.50 g) is weighed and slowly sprinkled into the previously prepared liquid that has reached 45°C without agglomeration. The beaker is covered and mixing continues. Within 15 minutes, the temperature of the mixture is brought to above 50°C, but not more than 80°C. While maintaining this temperature range, heating is continued for 2.5 hours with gentle stirring. After 2.5 hours, the beaker is removed from the hot plate and cooled to below 40°C. Next, 1.8 ± 0.2 mL of a 10% v / v lactic acid aqueous solution is added and mixed thoroughly. The mucus fraction mixture is autoclaved at 121°C for 15 minutes and cooled for 5 minutes. The mixture of mucus components was removed from the autoclave and stirred until the temperature reached 23°C ± 1°C.

[0182] Allow the temperature of the sheep blood and mucus components to reach 23°C ± 1°C. Using a 500 mL graduated cylinder, measure the volume of the entire batch of previously prepared mucus components and add it to a 1200 mL beaker. Add an equal amount of sheep blood to the beaker and mix thoroughly. Using the viscosity method described above, ensure that the viscosity of the AMF is between 7.15-8.65 centistokes. If not, dispose of the batch and make another batch as needed for adjusting the mucus component.

[0183] Unless intended for immediate use, qualified AMF should be refrigerated at 4°C. After preparation, AMF may be stored in an airtight container at 4°C for up to 48 hours. Prior to testing, the AMF must be brought to 23°C ± 1°C. After testing is complete, discard any unused portion.

[0184] Examples / Data

[0185] Provide following data and embodiment (comprising comparative example) to help illustrate upper nonwoven layer and lower nonwoven layer, absorbent core structure and / or absorbent article described herein.Illustrated structure is provided only for illustrative purposes and can not be understood as limitation to the present disclosure, because can have many variations when not departing from the spirit and scope of the present invention.

[0186] Nonwoven Material Testing

[0187] The nonwoven layer material is tested to evaluate the ability of the nonwoven material to strain (elongate) and recover its initial state (simulating physical deformation in use) under balanced stretching. Samples FH are comparative examples. The CD cyclic extension to 3% strain method and the breaking strain method described herein are tested. The results are shown in Table 1.

[0188] Table 1: Nonwoven materials tested in the CD cyclic extension to 3% strain method and the break strain method

[0189]

[0190]

[0191] 1 ATB Z87G-40 was purchased from Xiamen Yanjan New Material Co. (China)

[0192] 2 by 53FC041001 purchased from Sandler GmbH (Germany)

[0193] 3 by 553FC041005 (option 82) from Sandler GmbH (Germany)

[0194] 4 Purchased from Xiamen Yanjan New Material Co. (China) as Aura 20

[0195] 5 Purchased from Jacob Holms Industries (Germany) as S25000541R01

[0196] 6 PFNZN 18G BICO8020 PHI 6 was purchased from dPFNonwovens Czech SRO (Czech Republic)

[0197] 7 PEGZN25 BICO7030 Phobic was purchased from dPFNonwovens Czech SRO (Czech Republic)

[0198] 8 Purchased from Dunn Paper (USA) at 3028

[0199] It is found that suitable nonwoven layer materials are strained (stretched) with balanced stretching to recovery behavior. If the nonwoven layer material plastically stretches (that is, stretches but does not recover) as the fluff / AGM matrix in the inner core layer stretches, then there will not be enough recovery energy to return to the initial, pre-stretched state, and the nonwoven layer material will become permanently strained (stretched). The top nonwoven layer of the present disclosure can have a permanent strain value less than about 0.013. At the same time, if the nonwoven layer material is strained violently, for example, greater than 5%, the nonwoven layer material needs to maintain its integrity and not tear or break (see, for example, sample H, which tears and has a break strain less than 5%). The nonwoven layer of the present disclosure can have a break strain greater than about 10%.

[0200] The above nonwoven layer materials were also tested to evaluate the ability of the nonwoven material to bend and deform and to recover to its original state. The test was performed according to the wet and dry CD ultrasensitive 3-point bending method described herein. The results are shown in Table 2.

[0201] Table 2: Nonwoven materials tested in wet and dry CD ultrasensitive 3-point bending method

[0202]

[0203]

[0204] During walking, the absorbent article is compressed and bent left and right in a cyclic mode when the gap between her legs narrows, and then expands as her legs move. Not limited by theory, it is believed that the nonwoven layer material with dry bending energy less than about 2N*mm will allow this bending compression to occur easily, but will not be too hard to hinder bending compression. At the same time, after bending compression, the nonwoven layer needs to be able to maintain enough dry recovery energy so that the fluff / AGM matrix in the nonwoven layer and the inner core layer returns to its initial pre-bent state. The upper nonwoven layer of the present disclosure can have a dry recovery energy value greater than about 0.03N*mm.

[0205] Sample AE shows the dry peak load of 0.03N to 0.38N and the dry recovery energy of 0.032N*mm to 0.092N*mm, indicating that these materials are easy to bend and have enough dry recovery energy to recover their initial pre-bent state. As comparative examples, sample F and G show the dry peak load of 0.01N and 0.03N respectively and the dry recovery energy of 0.005N*mm and 0.019N*mm respectively, which shows that although these materials are easy to bend, they do not have enough recovery energy to recover their initial pre-bent state after compression. Sample H (comparative example) shows the dry peak load of 0.04N and the dry recovery energy of 0.031N*mm. However, it is found that sample H tears when getting wet, so that it is not enough to be used as the upper nonwoven layer and / or the lower nonwoven layer of the present disclosure.

[0206] Without being limited by theory, it is believed that the nonwoven layer material comprising thick fibers (about 2.0 dtex to about 10 dtex) arranged in a network structure is able to carry mechanical loads within the fiber network and return the absorbent core structure and / or absorbent article to its original shape after bending compression. Samples F and G comprise relatively fine fibers (less than about 2.0 dtex), while samples AE comprise a fiber blend having a fiber thickness of about 2.2 dtex to about 10 dtex.

[0207] Absorbent core structure test

[0208] The absorbent core structure is tested to evaluate the ability of the absorbent core structure to compress (simulate the compression experienced between the legs of the wearer) and return to its original state. The examples 1-3 in Table 3 show the absorbent core structures described herein. Comparative Examples AC are comparative examples. The descriptions of Examples 1-3 and Comparative Examples AC are listed in Table 3. The absorbent core structure is prepared as described below. The absorbent core structure is evaluated according to the wet and dry gathered compression method as described herein. The results are shown in Table 4.

[0209] Table 3: Absorbent core structure

[0210]

[0211] 1 ATB Z87G-40 was purchased from Xiamen Yanjan New Material Co. (China)

[0212] 3 by 553FC041005 (option 82) from Sandler GmbH (Germany)

[0213] 4 Purchased from Xiamen Yanjan New Material Co. (China) as Aura 20

[0214] 5 Purchased from Jacob Holms Industries (Germany) as S25000541R01

[0215] 6 PFNZN 18G BICO8020 PHI 6 was purchased from dPFNonwovens Czech SRO (Czech Republic)

[0216] 8 Purchased from Dunn Paper (USA) at 3028

[0217] 9Purchased from Evonik (Germany) as Favor SXM9745

[0218] 10 Purchased from Resolute Alabama (USA) as Item 9E3-COOSABSORB S

[0219] 11 Purchased from Fitesa (Germany) as Article 4004416 (MR 3585374)

[0220] The absorbent core structure listed in Table 3 is produced as described in detail in the specification. Specifically, first the upper nonwoven layer is introduced on the forming drum in the shelf section, and is pulled into a three-dimensional pocket shape under vacuum. The uniform flow of fluff (cellulose) and AGM material is directly deposited on the upper nonwoven layer in the forming station. Before entering the forming station, the upper nonwoven is coated with a spray adhesive (available from the Technomelt DM 9036U of Henkel (Germany), 6gsm continuous melt-blown spiral, 50mm is wide), to provide fluff (cellulose) and AGM and the stronger connection of the upper nonwoven, and do not hinder liquid from flowing into the fluff / AGM matrix. When leaving the shelf section, the lower nonwoven web is combined with the nonwoven of the uniform blend carrying fluff / AGM. The lower nonwoven was pre-coated with adhesive (Technomelt DM 9036U from Henkel (Germany)) to achieve a perimeter seal (10 gsm meltblown spiral, 20 mm wide on the sides), and a 6 gsm, 50 mm wide continuous meltblown spiral adhesive (Technomelt DM 9036U from Henkel (Germany)) was applied in the center to better integrate the fluff / AGM matrix.

[0221] Examples 1 to 3 and Comparative Examples A and B also have Figure 4 The structural bonding shown is Figure 5 The profile shown. Examples 1-3 and Comparative Examples AB have a structural bond spacing of 32 mm x 16 mm, resulting in a total structural bond site area of ​​1.38% of the total absorbent core structural area. Comparative Example C is the same as Comparative Example B, except that the structural bond spacing is 10 mm x 10 mm, resulting in a total structural bond site area of ​​6.28% of the total absorbent core structural area. The structural bonds are applied using a heated aluminum mold to produce the embossing pattern in a heated hydraulic press. The structural bond embossing plate has an area of ​​3.55 mm 2 And the height is about 1mm protrusion, such as Figure 4 As shown, Figure 5The structural bonds were spaced according to the spacing dimensions described above. The structural bonding embossing plate was heated to 120°C and set to a compression pressure of 170 kPa. The absorbent article was placed and oriented under the heated embossing plate on the bottom plate of the hydraulic press and a thin sheet of Teflon was placed before embossing. TM The film was placed on the sample to avoid melting of the top sheet fibers. The hydraulic press was started and compressed the sample for a dwell time of 1.7 seconds to create a structural bond pattern.

[0222] Examples 1-3 and Comparative Examples AC also have Figure 2C The flex bond channel areas are applied with a heated aluminum die to produce the embossed pattern in a heated hydraulic press. The flex bond channel embossing plate has protrusions spaced about 1.5 mm apart and are about 3 mm long and about 1.5 mm wide. The bond channel embossing plate is heated to 120°C and set to a compression pressure of 200 kPa. The absorbent article is placed and oriented under the heated embossing plate on the bottom plate of the hydraulic press and a thin piece of Teflon is placed before embossing. TM The film was placed on the sample to avoid melting of the top sheet fibers. The hydraulic press was started and compressed the sample for a dwell time of 1.7 seconds to produce a knot embossing pattern.

[0223] Table 4: Absorbent core structures measured in wet and dry gathered compression methods

[0224]

[0225]

[0226] The absorbent core structure that discovery comprises the nonwoven layer material with enough elasticity and recovery energy can return to the original absorbent core structure shape before compression.Embodiment 1-3 shows the fifth cycle wet recovery energy greater than 1.0N*mm and the fifth cycle wet maximum compression force of 207gf to 213gf.These structures show low compression force (less resistance, so it feels soft and pliable), but still can recover their shape when the structure is compressed and released in a cyclic manner.However, Comparative Example A-C shows the fifth cycle wet recovery energy of 0.26N*mm to 0.59N*mm.There is not enough recovery energy after five compression cycles, and Comparative Example A-C keeps compression, gathers state with the power (stored energy) that is not enough to recover its original shape before compression.

[0227] The absorbent core structures and / or absorbent articles of the present disclosure may have a fifth cycle wet recovery energy greater than about 1.0 N*mm, or from about 1.0 N*mm to about 3.5 N*mm. The absorbent core structures and / or absorbent articles of the present disclosure may have a fifth cycle wet maximum compression force greater than about 150 gf, preferably greater than about 200 gf, or from about 150 gf to about 225 gf.

[0228] It was found that although the nonwoven material alone may have sufficient % strain at break in the strain at break method, once combined into an absorbent core structure, the nonwoven material may not be able to provide sufficient recovery energy for the complete absorbent core structure (such as, for example, in Comparative Example A) to return to its original pre-compression shape. For example, in Comparative Example A, the basis weight and thickness of the fibers of the upper nonwoven material provide a fifth cycle wet recovery energy of less than 1.0 N*mm when combined with a thin lower nonwoven material.

[0229] Finished product testing

[0230] Absorbent articles are tested to evaluate the ability of the wrapped absorbent core structure to compress (simulate the compression experienced between the legs of the wearer) and return to its original state. Examples 4-7 show absorbent articles as described herein. Comparative Examples D and E are comparative examples. Comparative Example FL is a commercially available finished product. The descriptions of Examples 4-7 and Comparative Examples DE are listed in Table 5a. The description of Comparative Example FL is listed in Tables 5b and 5c. Examples 4-7 and Comparative Examples D and E are prepared as described below. The absorbent articles in Tables 5a and 5b are evaluated according to the wet and dry CD and MD 3-point bending method, the wet and dry gathered compression method, and the light touch rewetting method as described herein. The results are shown in Table 6.

[0231] Table 5a: Absorbent Article Description

[0232]

[0233] 1 ATB Z87G-40 was purchased from Xiamen Yanjan New Material Co. (China)

[0234] 2 by 53FC041001 purchased from Sandler GmbH (Germany)

[0235] 3 by 553FC041005 (option 82) from Sandler GmbH (Germany)

[0236] 4Purchased from Xiamen Yanjan New Material Co. (China) as Aura 20

[0237] 5 Purchased from Jacob Holms Industries (Germany) as S25000541R01

[0238] 6 PFNZN 18G BICO8020 PHI 6 was purchased from dPFNonwovens Czech SRO (Czech Republic)

[0239] 8 Purchased from Dunn Paper (USA) at 3028

[0240] 9 Purchased from Evonik (Germany) as Favor SXM9745

[0241] 10 Purchased from Resolute Alabama (USA) as Item 9E3-COOSABSORB S

[0242] 12 The nonwoven top sheet "Nonwoven SG" is a nonwoven web according to U.S. Patent Publication No. 2019 / 0380887.

[0243] Table 5b: Commercially available finished products :

[0244]

[0245]

[0246] Table 5c: Materials found in commercially available products (Comparative Examples F to L)

[0247]

[0248] Examples 4 to 7 and Comparative Examples D and E include structures as detailed in Table 3 as in Examples 1 to 3, with the same adhesive design and the same 32 mm × 16 mm structural bonding pattern in the absorbent core structure (the total structural bonding area is 1.38% of the total area of ​​the absorbent core structure). In addition, the absorbent article includes a nonwoven top sheet web as detailed in U.S. Patent Publication No. 2019 / 0380887, which is bonded to the absorbent core structure with a spray adhesive application (Technomelt DM 9036U purchased from Henkel (Germany), 3gsm continuous meltblown spiral, 50mm wide, 150mm long). In addition, a 12gsm polypropylene backsheet is bonded to the outward-facing surface of the lower nonwoven with a spray adhesive application (Technomelt DM 9036U purchased from Henkel (Germany), 3gsm continuous meltblown spiral, 50mm wide, 150mm long).

[0249] Examples 4-7 and Comparative Examples D and E also have Figure 4 The structural bonding shown is Figure 5 The profile shown. Structural bonding is applied using a heated aluminum die to create the embossing pattern within a heated hydraulic press. The structural bonding embossing press plate has an area of ​​3.55mm 2 And the height is about 1mm protrusion, such as Figure 4 As shown, Figure 5 The structural bonds were spaced according to the spacing dimensions described above. The structural bonding embossing plate was heated to 120°C and set to a compression pressure of 170 kPa. The absorbent article was placed and oriented under the heated embossing plate on the bottom plate of the hydraulic press and a thin sheet of Teflon was placed before embossing. TM The film was placed on the sample to avoid melting of the top sheet fibers. The hydraulic press was started and compressed the sample for a dwell time of 1.7 seconds to create a structural bond pattern.

[0250] Prior to backsheet bonding, flex bond channel regions were applied to Examples 4-7 and Comparative Examples D and E, which had Figure 2C The flex bond channel area was applied with a heated aluminum die to create the embossing pattern in a heated hydraulic press. The channel embossing plate had protrusions spaced about 1.5 mm apart and were about 3 mm long and about 1.5 mm wide. The bond channel embossing plate was heated to 120°C and set to a compression pressure of 200 kPa. The absorbent article was placed and oriented underneath the heated embossing plate on the bottom plate of the hydraulic press and a thin sheet of Teflon was placed on top prior to embossing. TM The film was placed on the sample to avoid melting of the top sheet fibers. The hydraulic press was started and compressed the sample for a dwell time of 1.7 seconds to produce a knot embossing pattern.

[0251] Table 6: Tested in wet and dry CD and MD 3-point bend method, wet and dry gathered compression method and light touch rewet method Absorbent products and commercially available finished products

[0252]

[0253]

[0254] It is believed that in order to provide high body conformability, the absorbent articles of the present disclosure may exhibit a strength of about 10 N.mm 2 To about 30N.mm 2 , or about 10N.mm 2 To about 25N.mm 2 In addition, it is believed that in order to provide an absorbent article that can be compressed with body movement and recover to its original pre-compression state against the user's body, the absorbent article of the present disclosure can have a fifth cycle wet recovery energy of about 1.0 N.mm to about 3.5 N.mm and / or a fifth cycle wet recovery of about 29% to about 40%. The absorbent article of the present disclosure can also maintain good fluid handling, which delivers a low light touch rewet of about 0g to about 0.15g.

[0255] Examples 4-7 showed 13.0 N.mm in both wet and dry bunched compression methods. 2 Up to 18.7N.mm 2 CD dry bending stiffness and 5th cycle wet recovery of 29% to 36%, demonstrating that these structures will be able to maintain their shape in use. Comparative Examples D and E exhibited 9.1 N.mm 2 and 13.0N.mm 2 CD dry bending stiffness. However, Comparative Examples D and E exhibited a fifth cycle wet recovery of less than 29% in the wet and dry bunched compression method, indicating that these structures will not be able to maintain their shape in use and will remain bunched. Comparative Example FL exhibited 29 N.mm 2 Up to 47.5N.mm 2 The CD dry bending stiffness of is (indicating that the structure is less flexible and less able to conform), which is a commercially available product.

[0256] Without being limited by theory, it is believed that in order to maintain comfortable shape recovery after compression, sufficient recovery energy is required to push the absorbent article on the underwear back to its pre-compression shape. At the same time, the absorbent article (via the absorbent core structure) needs to recover along the same path as the compression to return to its pre-compression position. If the fifth cycle wet recovery energy is less than about 1.0N.mm, the absorbent article may not have the recovery energy required to recover its shape. If the fifth cycle wet recovery energy value is too high, the recovery may be too strong, making the wearer feel like the absorbent article is not staying in place. If the fifth cycle wet recovery % value is low (less than about 29%), the absorbent article may not return to its pre-compression shape and may remain deformed and gathered. If the fifth cycle wet recovery % value is too high (greater than about 40%), it indicates that when the absorbent article is first applied to the wearer's underwear, the absorbent article may be too strongly restored to a flat shape, which is contrary to the shape that fits her body.

[0257] Structural Bond Testing

[0258] The absorbent core structures were tested to evaluate the effect of structural bonding area on flexibility and bending stiffness. Example 8 did not feature any structural bonding within the absorbent core structure. Examples 9 and 10 had Figure 4 The structural bonding shown is Figure 5 The results of the wet and dry MD 3-point bend method are shown in Table 7.

[0259] Table 7: Polypropylene films according to the present invention with different structural bonding areas tested in wet and dry CD and MD 3-point bend method Absorbent core structure .

[0260]

[0261] 3 by 553FC041005 (option 82) from Sandler GmbH (Germany)

[0262] 9 Purchased from Evonik (Germany) as Favor SXM9745

[0263] 10 Purchased from Resolute Alabama (USA) as Item 9E3-COOSABSORB S

[0264] 13 Purchased from Industries SpA. (Italy) at 10SMS PHILIC

[0265] Table 7 demonstrates the effect of total structural bond area and spacing. Figure 4 The asymmetric structure bonding shape shown and Figure 5 The profile shown has a 3.55mm 2 The maximum area of ​​the MD dry bending stiffness was found to increase with the increase of the structural bonding area. Example 8 showed 9.8 N.mm 2 MD dry bending stiffness with non-structural bonding. Example 9 exhibits 19.2 N.mm 2 MD dry bending stiffness of 32mm x 16mm with a structural bond spacing (total structural bond site area is 1.38% of the total absorbent core structure area). Example 10 exhibits 29.6N.mm 2 MD dry bending stiffness with a structural bond spacing of 16 mm x 16 mm (the total structural bond site area is 3.96% of the total area of ​​the absorbent core structure). It is believed that in order to maintain a flexible and conformable absorbent core structure and / or absorbent article in the front-to-back (MD) direction of wear, the absorbent core structure and / or absorbent article may have a MD dry bending stiffness of about 10 N.mm 2 To about 30N.mm 2 MD stem bending stiffness.

[0266] The absorbent core structure listed in Table 7 is produced as described in detail in the specification. Specifically, first 50gsm elastic jet spunlace 6 upper nonwoven fabric is introduced on the forming drum in the shelf section, and is pulled into a three-dimensional pocket shape under vacuum. The uniform flow of fluff (cellulose) and AGM material is directly deposited on the upper nonwoven material in the forming station. Before entering the forming station, the upper nonwoven fabric is coated with a spray adhesive (available from the Technomelt DM 9036U of Henkel (Germany), 6gsm continuous melt-blown spiral, 50mm is wide), to provide fluff (cellulose) and AGM and the stronger connection of the upper nonwoven fabric, and do not hinder liquid from flowing into the fluff / AGM agglomerate. When leaving the shelf section, the nonwoven fabric combination of the 10gsm SMS bottom nonwoven web and the uniform blend carrying fluff (cellulose) and AGM layer. The lower nonwoven was pre-coated with adhesive (Technomelt DM 9036U from Henkel (Germany)) to achieve a perimeter seal (10 gsm meltblown spiral, 20 mm wide on the sides) and a 6 gsm, 50 mm wide continuous meltblown spiral adhesive was applied in the center to better integrate the fluff / AGM mass. Figure 4 The structural bonding shown is Figure 5The profile shown is applied to Examples 9 and 10. The structural bonding of Example 9 has a spacing of 32mm×16mm, thereby occupying a total structural bonding position area of ​​1.38% of the total area of ​​the absorbent core structure. The structural bonding of Example 10 has a spacing of 16mm×16mm, thereby occupying a total structural bonding position area of ​​3.96% of the total area of ​​the absorbent core structure with this structural bonding profile. The total area of ​​the absorbent core structure is measured according to the structural bonding position pattern spacing and area measurement method. Structural bonding is applied using the same method as described above for Examples 1-3 and Comparative Examples AB.

[0267] Combination / Example

[0268] A. A disposable absorbent article comprising: a top sheet; a back sheet; and an absorbent core structure disposed between the top sheet and the back sheet, wherein the absorbent core structure comprises: (a)

[0269] (a) an upper nonwoven layer comprising polymer fibers and having a basis weight of 35 gsm to 85 gsm; (b) a lower nonwoven layer comprising polymer fibers and having a basis weight of 10 gsm to 40 gsm; and (c) an inner core layer disposed between the upper nonwoven layer and the lower nonwoven layer, wherein the inner core layer comprises 50% to 85% cellulose fibers by weight of the inner core layer, and 15% to 50% superabsorbent particles by weight of the inner core layer, and wherein the absorbent core structure has an average density between 0.045 g / cm3 and 0.15 g / cm3; wherein the inner core layer is contained within the upper nonwoven layer and the lower nonwoven layer by substantially sealing at least the left and right regions of the upper nonwoven layer and the lower nonwoven layer at a peripheral seal.

[0270] B. A disposable absorbent article according to paragraph A, wherein the absorbent core structure comprises a plurality of structural bonding sites; wherein the structural bonding sites have a bonding area of ​​2 mm2 to 5 mm2, as measured according to the structural bonding site pattern spacing and area measurement method.

[0271] C. The disposable absorbent article of paragraph B, wherein the total structural bond area of ​​the absorbent core structure is from 0.75% to 4.5% of the absorbent core structure as measured according to the Structural Bond Site Pattern Spacing and Area Measurement Method.

[0272] D. A disposable absorbent article according to paragraphs BC, wherein the average distance between the structural bonds is 10 mm to 32 mm, as measured according to the Structural Bond Pattern Spacing and Area Measurement Method.

[0273] E. The disposable absorbent article of paragraphs BD, wherein the upper nonwoven layer and the lower nonwoven layer are brought closer together in the Z direction at the structural bond site, but are not melted together.

[0274] F. The disposable absorbent article of paragraphs AE, wherein the polymer fibers of the upper nonwoven layer are selected from polyethylene terephthalate, polypropylene, polylactic acid, bicomponent fibers comprising polyethylene / polypropylene or polyethylene / polyethylene terephthalate, and combinations thereof.

[0275] G. A disposable absorbent article according to paragraphs AF, wherein the polymer fibers of the lower nonwoven layer are selected from polyethylene terephthalate, polypropylene, polylactic acid, bicomponent fibers comprising polyethylene / polypropylene or polyethylene / polyethylene terephthalate, and combinations thereof.

[0276] H. The disposable absorbent article of paragraphs AG, wherein the absorbent article has a dry thickness of between about 2.0 mm and about 6.0 mm as measured according to the Wet and Dry CD and MD 3-Point Method.

[0277] I. The disposable absorbent article of paragraphs AH, wherein the polymer fibers of the upper nonwoven layer have a fiber length of 10 mm to 100 mm, preferably 20 mm to 50 mm.

[0278] J. The disposable absorbent article of paragraph AI, wherein the polymer fibers of the upper nonwoven layer have a fiber diameter of 2.0 to 10 dtex, and the polymer fibers of the lower nonwoven layer have a fiber diameter of 1.7 to 5 dtex.

[0279] K. The disposable absorbent article of paragraphs AJ, wherein the polymer fibers of the upper nonwoven layer comprise 70% to 100% synthetic fibers and 0% to 40% regenerated cellulose fibers including rayon.

[0280] L. A disposable absorbent article according to paragraphs AK, wherein the upper nonwoven layer has a tensile stiffness of 0.3 N / mm to 1.6 N / mm, as measured by the CD cyclic extension to 3% strain method, and a breaking strain of 10% to 50%, preferably 20% to 40%, as measured by the breaking strain method.

[0281] M. The disposable absorbent article of paragraph AL, wherein the upper nonwoven layer has a tensile stiffness of about 0.3 N / mm to about 1.0 N / mm as measured according to the CD Cyclic Extension to 3% Strain method.

[0282] N. The disposable absorbent article of paragraph AM, wherein the lower nonwoven layer has a permanent strain of 0.005 mm / mm to 0.013 mm / mm as measured according to the CD Cyclic Extension to 3% Strain method.

[0283] O. The disposable absorbent article of paragraphs AN, wherein the absorbent article has a Touch Rewet value of 0 grams to 0.15 grams, as measured according to the Touch Rewet method.

[0284] P. The disposable absorbent article of paragraph AO, wherein the upper nonwoven layer is a through-air bonded nonwoven or a hydroentangled nonwoven.

[0285] The dimensions and values ​​disclosed herein are not to be understood as being strictly limited to the exact numerical values ​​cited. Instead, unless otherwise indicated, each such dimension is intended to represent the stated value and a functionally equivalent range around that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm".

[0286] Unless expressly excluded or otherwise limited, each document cited herein, including any cross-referenced or related patent or application, is incorporated herein by reference in its entirety. Citation of any document is not an admission that it is prior art to any of the present invention disclosed or claimed herein, or that it, by itself or in combination with any one or more references, proposes, suggests, or discloses any such invention. In addition, to the extent that any meaning or definition of a term in this invention conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this invention shall govern.

[0287] Although specific embodiments of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended that all such changes and modifications within the scope of the present invention be covered in the appended claims.

Claims

1. A disposable absorbent article, comprising: Top sheet; negative film; as well as An absorbent core structure, the absorbent core structure being disposed between the top sheet and the back sheet, wherein the absorbent core structure comprises: a. an upper nonwoven layer comprising polymer fibers and having a basis weight of 35 gsm to 85 gsm; b. a lower nonwoven layer comprising polymer fibers and having a basis weight of from 10 gsm to 40 gsm; and c. an inner core layer disposed between the upper nonwoven layer and the lower nonwoven layer, wherein the inner core layer comprises 50% to 85% cellulose fibers by weight of the inner core layer and 15% to 50% superabsorbent particles by weight of the inner core layer, and wherein the absorbent core structure has a molecular weight between 0.045 g / cm 3 and 0.15g / cm 3 The average density between Wherein the inner core layer is contained within the upper nonwoven layer and the lower nonwoven layer by substantially sealing at least left and right regions of the upper nonwoven layer and the lower nonwoven layer at a peripheral seal.

2. The disposable absorbent article according to claim 1, wherein the absorbent core structure comprises a plurality of structural bonding sites; wherein the structural bonding sites have a 2 mm 2 Up to 5mm 2 The bond area as measured according to the Structural Bond Pattern Spacing and Area Measurement Method.

3. The disposable absorbent article of claim 2, wherein the total structural bond area of ​​the absorbent core structure is from 0.75% to 4.5% of the absorbent core structure as measured according to the Structural Bond Site Pattern Spacing and Area Measurement Method.

4. The disposable absorbent article of claim 2 or 3, wherein the average distance between the structural bonds is from 10 mm to 32 mm, as measured according to the Structural Bond Pattern Spacing and Area Measurement Method.

5. The disposable absorbent article according to any one of claims 2 to 4, wherein the upper nonwoven layer and the lower nonwoven layer are brought closer together in the Z direction at the structural bonding site but are not melted together.

6. The disposable absorbent article according to any of the preceding claims, wherein the polymer fibers of the upper nonwoven layer are selected from polyethylene terephthalate, polypropylene, polylactic acid, bicomponent fibers comprising polyethylene / polypropylene or polyethylene / polyethylene terephthalate, and combinations thereof.

7. The disposable absorbent article according to any one of the preceding claims, wherein the absorbent article has a dry thickness of between about 2.0 mm and about 6.0 mm as measured according to the Wet and Dry CD and MD 3-point method.

8. The disposable absorbent article according to any one of the preceding claims, wherein the polymer fibers of the upper nonwoven layer have a fiber length of 10 mm to 100 mm, preferably 20 mm to 50 mm.

9. The disposable absorbent article according to any one of the preceding claims, wherein the polymer fibers of the upper nonwoven layer have a fiber diameter of 2.0 to 10 dtex and the polymer fibers of the lower nonwoven layer have a fiber diameter of 1.7 to 5 dtex.

10. The disposable absorbent article according to any one of the preceding claims, wherein the polymer fibers of the upper nonwoven layer comprise 70% to 100% synthetic fibers and 0% to 40% regenerated cellulose fibers including rayon.

11. A disposable absorbent article according to any of the preceding claims, wherein the upper nonwoven layer has a tensile stiffness of 0.3 N / mm to 1.6 N / mm, as measured by the CD cyclic extension to 3% strain method, and a strain at break of 10% to 50%, preferably 20% to 40%, as measured by the strain at break method.

12. The disposable absorbent article of any one of the preceding claims, wherein the upper nonwoven layer has a tensile stiffness of about 0.3 N / mm to about 1.0 N / mm as measured according to the CD Cyclic Extension to 3% Strain method.

13. The disposable absorbent article according to any one of the preceding claims, wherein the lower nonwoven layer has a permanent strain of 0.005 mm / mm to 0.013 mm / mm as measured according to the CD Cyclic Elongation to 3% Strain method.

14. The disposable absorbent article according to any one of the preceding claims, wherein the absorbent article has a Touch Rewet value of 0 grams to 0.15 grams as measured according to the Touch Rewet method.

15. The disposable absorbent article according to any one of the preceding claims, wherein the upper nonwoven layer is a through-air bonded nonwoven or a hydroentangled nonwoven.

Citation Information

Patent Citations

  • Apertured macroscopically expanded three-dimensional polymeric web exhibiting breatheability and resistance to fluid transmission and use thereof in an absorbent article

    EP0203821A2

  • Breathable backsheet design for disposable absorbent articles

    EP0710471A1

  • Breathable dual layer backsheet design for disposable absorbent articles

    EP0710472A1

  • Absorbent articles having fluid contact angle gradients between the topsheet and absorbent core

    EP0793952A1

  • Fluid management layer for an absorbent article

    US12138146B2